A low-latitude, high-elevation 10Be production-rate calibration from the Rwenzori Mountains, Uganda - Nathan Anderson; Margaret S. Jackson; Meredith A. Kelly; James M. Russell; Andrea L. Mason; Sloane Garelick; Alice M. Doughty; Bob Nakileza; Laura Hutchinson; George R. Geier; Alan J. Hidy (Quaternary Geochronology, 2026)

The association between objective and perceived bird diversity and the mental health of minoritized communities living near disused parks in Detroit - Christopher J. Dennison; Katherine Mason; Amber L. Pearson; Rachel T. Buxton (Landscape and Urban Planning, 2026)

Treatment of PFAS-impacted saline purge waters by the ultraviolet/boron nitride photo(cata)lytic process - Laura DiGiacomo; Eman Z. Alhamdan; Marc M. Mason; Ezra L. Cates (Journal of Water Process Engineering, 2026)

Meet me in the middle: potential collaborative benthic hunting in humpback whales (Megaptera novaeangliae) - David N. Wiley; David E. Cade; Ari S. Friedlaender; Jeremy Goldbogen; Jessica Kendall-Bar; Susan E. Parks; Michael A. Thompson; Mason Weinrich; Tammy L. Silva (Behavioral Ecology and Sociobiology, 2026)
Cooperative hunting, in its numerous forms, has implications for animal cognition and social evolution. We used multi-sensor acoustic/video recording tags attached to free-swimming humpback whales (Megaptera novaeangliae) to provide the species’ first documentation of cooperative, coordinated benthic hunting and evidence supporting collaboration, the most cognitively complex level of hunting. Collaborative hunting, consisting of the tagged whale and 1–3 co-hunters, comprised 79% ( n = 110) of observed benthic-hunting events. Hunting animals concurrently arrived at the seafloor and simultaneously moved towards co-hunters, forming a head-to-head configuration that terminated when rostrums were within meters of each other; a behavior that could be seen to drive/corral sand lance ( Ammodytes dubius ) prey towards co-hunter(s). Tagged animals changed their direction of attack for each event, but co-hunters typically realigned into the same relative position, based on that of co-hunters. Using a clock position method, in relation to the tagged animal’s heading (12:00; n = 87), co-hunters occupied the 1:00 position most frequently (59%), followed by 11:00 (35%), 12:00 (12%), 3:00 (5%), and 2:00 (2%). The 1:00 and 11:00 locations would be optimal prey herding/capture positions. In events where all co-hunters were identified, individuals assumed the same position in 93.1% of events ( n = 54). Animals opened their mouths for prey capture in near unison (mean offset 3.7 s, SD 5.3 s, n = 43). The fission-fusion, non-kin-based social system of humpback whales makes them an unlikely species to evolve collaborative hunting. We speculate that the need to capture small, evasive prey, combined with cognitively driven behavioral plasticity contribute to the evolution of this hunting strategy.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Innovating Mobility: A Student Competition in Wheel and Track Design - Devin Chen; Chaitanya Shekhar Sonalkar; Riku Kikuta; Andries Peenze; Varsha S. Swamy; J. Ethan Salmon; Bohumir Jelinek; George L. Mason; P. Schalk Els; Corina Sandu (Journal of Terramechanics, 2026)

Comparative transcriptomics of adherent and suspension chicken fibroblast cell lines for the optimization of cultivated meat processes - Elizabeth J. Contreras; Archana Nagarajan; Benjamin H. Bromberg; Mason P. Villegas; David L. Kaplan (Food Research International, 2026)

Nonlinear relationships between deer harvests, agriculture, and deer-vehicle collisions - Mark E. Bell; David S. Mason; Kenneth F. Kellner; Jacob E. Hill; Chad Stewart; Jerrold L. Belant (Environmental Impact Assessment Review, 2026)

Evaluating bidirectional, longitudinal associations between adolescent executive control and eating behaviors - Hope Thilges; Eric M. Phillips; Emily L. Goldberg; Rebecca L. Brock; Katherine M. Kidwell; Amy Lazarus Yaroch; Jennie L. Hill; Kimberly Andrews Espy; Jennifer Mize Nelson; W. Alex Mason; Timothy D. Nelson (Appetite, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Examining longitudinal associations between early environmental deprivation and unpredictability and dietary quality and eating behaviors a decade later - Emily L. Goldberg; Rebecca L. Brock; Amy Lazarus Yaroch; Jennie L. Hill; W. Alex Mason; Jennifer Mize Nelson; Kimberly Andrews Espy; Timothy D. Nelson (Appetite, 2026)

Interpretable forecasting of dissolved oxygen leveraging foundation model for proactive aeration in rural wastewater treatment systems - Jeimy L Martinez De La Hoz; Mahathir Mohammad Bappy; MD Shafikul Islam; Mason Marcantel; Michael P. Hayes (Water Research, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Select genotypes of white and green ash show heritable, elevated resistance to emerald ash borer - Mary E. Mason; Dave W. Carey; Jeanne Romero-Severson; Kathleen S. Knight; Therese M. Poland; Jennifer L. Koch (New Forests, 2026)

Semi-natural grasslands as a nature-based solution for climate change mitigation: An assessment of carbon and plant communities across age gradients - Tamsin Lockwood; Jessica L. Elias; Melanie Stone; Hannah R. Kemp; Melanie Spiers; Becky Davess; Nicholas Izard; Emily Mason; Jodie Hartill; Mike D. Morecroft (Agriculture, Ecosystems & Environment, 2026)

Cross‐Continental Ecological Drivers Behind Trait Clines in the Forest Grass Milium effusum - Charlotte Møller; Pieter De Frenne; J. Mason Heberling; Jesse Bellemare; Jörg Brunet; Hans Henrik Bruun; Jacques Cayouette; Guillaume Decocq; Martin Diekmann; Božo Frajman; Jenny Hagenblad; Per‐Ola Hedwall; et al. (Global Ecology and Biogeography, 2026)
Aim Widespread species encounter a range of variable climates that can lead to intraspecific trait clines. Such clines can be the result of phenotypic plasticity, genetic differences, or both. Although latitude often explains a large part of trait variation, it is crucial to investigate the underlying environmental variables to understand current and future trait responses. Cross‐continental comparisons of species that are native on multiple continents provide a rarely used approach that can help identify the environmental drivers of intraspecific trait clines. Location Europe and North America. Time Period 2021–2023. Major Taxa Studied Milium effusum L. (Poaceae). Methods To quantify the influence of environmental gradients on functional traits across geographical regions that vary in climate, we sampled M. effusum seeds from 23 European and 14 North American populations and transplanted them in a common garden. We measured 10 vegetative, reproductive, and phenological traits. We used 30‐year averages of 19 bioclimatic variables, while accounting for the latitudinal and elevational position of the population origins, to compare the trait‐environment relationships between continents. Results Our results showed that European populations occupy a broader climatic range than North American populations. Differences between continents were found in most of the traits as well as in the multivariate trait space. The traits were affected more by bioclimatic variables than by latitude or elevation. While flowering, leaf thickness, specific leaf area, and reproductive height showed parallel clines to the environment between continents, vegetative height and biomass showed contrasting clines. Main Conclusions Environmental influences from population origins revealed parallel clines between the continents for functional traits, suggesting shared selective pressures, while contrasting clines for plant size indicated different evolutionary trajectories, potential bottlenecks, or interactions with unknown ecological factors. This study highlights the complex interplay of genetic, environmental, and evolutionary factors in shaping phenotypic variation in native species across continents.

Comparing Navcam dust devil detections to transient daytime convective vortex signatures in REMS pressure and ultraviolet data - Emily L. Mason; Scott D. Guzewich; Christopher Edwards; Álvaro Vicente-Retortillo; Daniel Viúdez-Moreiras (Icarus, 2025)

The Martian oxygen green line dayglow: response to solar activity - L. Soret; H. Robin; J.-C. Gérard; L. Gkouvelis; I. Thomas; B. Ristic; Y. Willame; B. Hubert; A.C. Vandaele; J.P. Mason; F. Daerden; M.R. Patel (Icarus, 2025)

Chronic sublethal exposure to methylmercury lengthens telomeres in developing zebra finches - Rachel L. Davis; Samuel D. Mason; Christian Wake; Giulia Fabozzi; William L. Catalano; Chaim A. Schramm; Amy R. Henry; Cokie L. Parker; Farida Laboune; Casey L. McLaughlin; Jeffrey D. Kittilson; John P. Swaddle; et al. (Environmental Pollution, 2025)

Overexpression of the NEK8 kinase inhibits homologous recombination - Joshua L. Turner; Georgia Moore; Tyler J. McCraw; Jennifer M. Mason (DNA Repair, 2025)

To Count or Not to Count: Appropriate Use of Calorie Counts in the Acute Care Setting - K. Kittridge; M. Creech; P. Mason; E. Denbow; E. Magnuson; L. Williams (Journal of the Academy of Nutrition and Dietetics, 2025)

Copper and zinc isotopic variation in Apollo 17 double drive tube 73001/2 reveals space weathering history of lunar regolith - Megan Broussard; Mason Neuman; Piers Koefoed; Frédéric Moynier; Nicole X. Nie; Richard V. Morris; Bradley L. Jolliff; Kun Wang (Geochimica et Cosmochimica Acta, 2025)

Stability of macroinvertebrate communities in vernal ponds following natural drying and refilling events - Mason S. Ward; Alice M. Belskis; Sara L. Hermann; Jon N. Sweetman (Wetlands Ecology and Management, 2025)
Vernal ponds are vital components of forest ecosystems in the eastern United States, providing biodiversity support, water filtration, and flood regulation. Climate change may exacerbate hydrological fluctuations, altering the communities these seasonal wetlands support. This study examines the effects of drying disturbances on macroinvertebrate communities in vernal ponds, focusing on comparing biodiversity metrics before and after hydrological drawdown. We conducted weekly monitoring of pond inundation and macroinvertebrate sampling in five vernal ponds in Central Pennsylvania during 2023. We measured alpha diversity using species richness and Shannon diversity, and calculated temporal beta diversity with Jaccard’s dissimilarity index, examining turnover and nestedness. We found no significant changes in alpha diversity metrics between pre- and post-drying periods. However, we observed a trend toward greater species loss (77% of dissimilarity) compared to gains (23%). Beta diversity patterns of turnover and nestedness were stable across temporal and spatial scales, suggesting that drying disturbances did not significantly affect community structure. These findings contrast with previous studies reporting significant shifts in community composition, potentially due to the adaptive strategies of macroinvertebrates. This research highlights the need for long-term studies to assess drying intensity and informs conservation strategies for vernal pond ecosystems in the context of climate change.

Low to moderate doses of 3-methylmethcathinone (3-MMC) produce analgesic effects in healthy volunteers: a proof of principle study with a designer drug - Johannes G Ramaekers; Johannes T Reckweg; Natasha L Mason; Kim PC Kuypers; Stefan W Toennes; Eef L Theunissen (Psychopharmacology, 2025)
3-Methylmethcathinone (3-MMC) is a synthetic cathinone that has been scheduled in many jurisdictions after it appeared on the consumer market as a designer drug or “legal high”. At present, there are no medical applications for synthetic cathinones, but in the past cathinone and other compounds that are structurally related to amphetamine have been evaluated and recognized for their intrinsic analgesic quality. The present study aimed to assess the analgesic effects of low to moderate doses (25, 50 and 100 mg) of 3-MMC in healthy volunteers ( N = 14) in a cross-over, placebo-controlled study. Participants were repeatedly exposed to experimental pain for up to 5 h after dosing in pressure pain threshold (PPT) and cold pressor test (CPT) paradigms. A profile of mood states questionnaire was used to assess the subjective effects of 3-MMC. Overall, 3-MMC produced dose-related elevations in pressure pain threshold and reduced subjective painfulness and unpleasantness in both experimental pain models. The analgesic effects of 3-MMC were most prominent after the 50 and 100 mg dose and persisted consistently for up to 5 h after dosing. 3-MMC also produced dose-related increments in mood that were prominent at 1 h, but not at 5 h after dosing. It is concluded that 3-MMC produces prolonged analgesic effects at doses that appear low enough to avoid a challenging subjective experience and that have been associated with a benign side effect profile. The present data warrant further research into the analgesic effects of low to moderate doses of 3-MMC in patient populations.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Diffusive gradients in thin films (DGT) for measuring potentially bioavailable pesticide residues in soil systems: Current challenges and perspectives - Vijay Kumar Aralappanavar; Binoy Sarkar; Casey L. Doolette; Leigh Donnellan; Sean Mason; Michael Rose; Peter Hoffmann; Hao Zhang; Enzo Lombi (Critical Reviews in Environmental Science and Technology, 2025)

Long term assessment of SARS-CoV-2 in wastewater and the transition to evaluate additional viral targets - Ayaaz Amirali; Mark E. Sharkey; Shruti Choudhary; Kristina M. Babler; Cynthia C. Beaver; Pratim Biswas; Kate R. Bowie; Taylor Burke; Benjamin B. Currall; George S. Grills; Hannah G. Healy; Alexander G. Lucaci; et al. (Science of The Total Environment, 2025)

Precession-driven variations in phosphorus cycling facilitated Earth’s oxygenation in the early Proterozoic - Wytze K. Lenstra; Margriet L. Lantink; Rick Hennekam; Paul R.D. Mason; Gert-Jan Reichart; Frederik J. Hilgen; Caroline P. Slomp (Chemical Geology, 2025)

The Mechanisms Through Which Fire Drives Population Change in Terrestrial Biota - Ella Plumanns‐Pouton; Julianna L. Santos; Cristina Aponte; Lluís Brotons; Luke T. Kelly; Stephen C. Mason; Kirsten Parris; Lauren Ponisio; David A. Keith (Global Change Biology, 2025)
Global fire regime change is threatening terrestrial biodiversity. Understanding how these changes affect biota is essential to protect biodiversity now and into the future. A targeted examination of the mechanisms through which fire influences populations will help achieve this by enabling comparisons and connections across taxa. Here, we develop a cross‐taxa framework that identifies mechanisms through which fire regimes influence terrestrial species populations over different time scales, and traits on which those mechanisms depend. We focus on amphibians, birds, fungi, insects, mammals, plants, and reptiles. First, we identify key mechanisms through which fire regimes influence species populations across different taxonomic groups. Second, we link these mechanisms to functional traits that influence the relevance to different species. Third, we identify traits that shape the vulnerability—or conversely, resilience—of species populations to frequent, high‐intensity, and large wildfires that are emerging as a threat in many parts of the world. Finally, we highlight how this integrative framework can be useful for understanding and identifying fire‐related threats common to different taxa across the globe and for guiding future research on fire‐related population change.

Impacts of Climate Change Interventions on Biodiversity, Water, the Food System and Human Health and Well‐Being - Pete Smith; Pramod K. Singh; Vedant P. Ballal; Francesco Cherubini; Julio Díaz‐José; Helena Duchková; Himangana Gupta; Masakazu Hori; Akihiko Ito; Shabana Khan; Marcos Llope; Maria Cristina Tirado; et al. (Global Change Biology, 2025)
Climate change threatens biodiversity, water, food and human health and well‐being. Rapid, sustained mitigation and adaptation actions can benefit all these elements of the nexus. Key transitions in energy, land and marine ecosystems, urban areas, industry and society are essential for climate change mitigation, adaptation and sustainable development. These transitions require interdisciplinary research, policy support and societal engagement. Here we present an assessment of 69 response options, a subset of which (15) was used in the climate change chapter of the IPBES Nexus Assessment. We show that the majority of climate change response options for land, oceans and ecosystems, settlement and infrastructure, industrial and societal system transitions have broadly positive impacts across the nexus. However, energy system transitions show more apparent trade‐offs. Most of these impacts result from energy infrastructure that would also be required for fossil fuel‐based systems and should be compared to the far more damaging consequences of continued fossil fuel use. Transitioning to cleaner, renewable energy sources reduces these risks and offers significant improvements across the nexus by reducing climate change impacts. Of the 69 response options assessed, 59% have entirely positive effects, or at least no negative effects, across all nexus elements and can be considered as low‐risk, immediately actionable options. The remaining 41% show either negative or variable impacts on at least one nexus element. However, this does not render them unviable; rather, their implementation must be carefully managed. Where impacts are variable, strategies should be tailored to ensure positive outcomes; where trade‐offs are unavoidable, efforts should focus on minimising negative effects and maximising synergies. Our findings suggest that prioritising policies that address the interconnected challenges of climate change, biodiversity loss, land degradation, pollution, food insecurity, access to clean water, energy for all and sustainable development will deliver more effective and equitable climate action.

Quantifying the Nutritional and Socio‐Ecological Dimensions of Indian Ocean Fisheries - Vania Andreoli; Jessica J. Meeuwig; Christopher D. Golden; Jessica Zamborain‐Mason; Laura G. Elsler; Maria L. D. Palomares; Dirk Zeller (Fish and Fisheries, 2025)
Seafood from marine fisheries, such as finfishes and invertebrates, is an important source of nutrients for billions of people globally. Seafood species vary in their micronutrient concentration, their economic value, and their vulnerability to exploitation and climate change. However, fisheries management has rarely considered the nutritional quality of fisheries catches and their relation to economic, conservation and climate vulnerability dimensions. Here, we quantified and analysed the micronutrient supply and average micronutrient concentration of taxa exploited by fisheries in the Indian Ocean. We also assessed associations among taxon‐specific micronutrient concentrations, ex‐vessel prices, fishing vulnerability and climate vulnerability. We found that small pelagic finfishes, despite contributing little to the overall catch weight, were particularly rich in micronutrients, were resilient and low priced, highlighting their utility in food and nutritional security. In contrast, taxa such as tunas and cephalopods were less nutrient‐dense, more vulnerable and had higher ex‐vessel prices. Results also showed differences in catch micronutrient concentrations between countries within the Indian Ocean Rim (IOR) and Distant Water Fishing (DWF) countries. IOR country catches were dominated by taxa richer in calcium, omega‐3 fatty acids and iron but with higher climate vulnerability. DWF catches, which accounted for only 2% of the Indian Ocean's total micronutrient supplies, were relatively richer in selenium, more vulnerable to fishing and had higher ex‐vessel prices. Our results highlight the trade‐offs and synergies among nutritional, economic, conservation and climate resilience dimensions of Indian Ocean fisheries, providing key insights for nutrition‐sensitive fisheries management strategies aimed at balancing multiple priorities.

Corrigendum to “Benthic deposition and burial of total mercury and methylmercury estimated using thorium isotopes in the high-latitude North Atlantic” [Geochim. et Cosmochimica Acta, 399 (2025) 191–204] - Xiangming Shi; Amber L. Annett; Rhiannon L. Jones; Rob Middag; Robert P. Mason (Geochimica et Cosmochimica Acta, 2025)

FBH1 and the replication stress response: Implications for genome stability and cancer development - Joshua L. Turner; Jennifer M. Mason (DNA Repair, 2025)

Benthic deposition and burial of total mercury and methylmercury estimated using thorium isotopes in the high-latitude North Atlantic - Xiangming Shi; Amber L. Annett; Rhiannon L. Jones; Rob Middag; Robert P. Mason (Geochimica et Cosmochimica Acta, 2025)

Downscaling global reference points to assess the sustainability of local fisheries - Jessica Zamborain‐Mason; Sean R. Connolly; M. Aaron MacNeil; Michele L. Barnes; Andrew G. Bauman; David A. Feary; Victor Huertas; Fraser A. Januchowski‐Hartley; Jacqueline D. Lau; Michalis Mihalitsis; Joshua E. Cinner (Conservation Biology, 2025)
Multispecies coral reef fisheries are typically managed by local communities who often lack research and monitoring capacity, which prevents estimation of well‐defined sustainable reference points to perform locally relevant fishery assessments. Recent research modeling coral reef fisheries globally has estimated multispecies sustainable reference points (i.e., the maximum reef fish yields that can be harvested sustainably and the corresponding reef fish standing biomass at which those are expected to be achieved) based on environmental indicators. These global reference points are a promising tool for assessing data‐poor reef fisheries but need to be downscaled to be relevant to resource practitioners. Using a small‐scale multispecies reef fishery in Papua New Guinea, we estimated sustainable reference points and assessed the sustainability of the fishery by integrating global‐scale analyses with local‐scale environmental conditions (i.e., coral cover, sea surface temperature, ocean productivity, and whether the reef is an atoll), reef area, fish catch and standing biomass estimates, and fishers’ perceptions. Local‐scale relevant data were obtained from a combination of remote sensing products, underwater visual censuses, catch surveys, and household structured social surveys. Our sustainability assessment based on downscaled estimated sustainable reference points was consistent with local fishers’ perceptions. Specifically, our downscaled results suggested that the fishing community was overfishing their reef fish stocks and stocks were below biomass levels that maximize production, making the overall reef fishery unsustainable. These results were consistent with fisher perceptions that reef fish stocks were declining in abundance and mean fish length and that fishers had to spend more time finding fish. Our downscaled site‐level assessment revealed severe local resource exploitation, the dynamics of which were masked in national‐scale assessments, emphasizing the importance of matching assessments to the scale of management. Overall, we show how global reference points can be applied locally when long‐term data are not available, providing baseline assessments for sustainably managing previously unassessed multispecies reef fisheries around the globe.

Potassium isotopic compositions and model exposure ages of lunar soils - Kun Wang; Zhen Tian; Megan Broussard; Mason Neuman; Piers Koefoed; Olga Pravdivtseva; Guillaume Avice; Richard V. Morris; Kees C. Welten; Randy L. Korotev; Bradley L. Jolliff (Geochimica et Cosmochimica Acta, 2025)

Equity in unilateral value chain policies: A monitoring framework for the EUDR and beyond - Constance L. McDermott; Thomas Addoah; Tawiah Agyarko-Kwarteng; Rebecca Asare; Alex Assanvo; Mairon Bastos Lima; Helen Bellfield; Amanda Berlan; Sophia Carodenuto; Toby Gardner; Rachael D. Garrett; Caitlin Hafferty; et al. (Forest Policy and Economics, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Tractive performance of rigid wheel in granular media using coarse-scale DEM models - Bohumir Jelinek; Angela Card; George L. Mason; Karl Grebner; Aidan Dickerson; Thomas Skorupa; Michael Cole; Jody D. Priddy (Journal of Terramechanics, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Correction: Progression and perceptual responses to blood flow restriction resistance training among people with multiple sclerosis - Ethan C. Hill; Jeffrey T. Schmidt; Kyle R. Reedy; Sean M. Lubiak; Chris E. Proppe; Paola M. Rivera; David H. Gonzalez Rojas; John E. Lawson; Anuj J. Prajapati; Niriham M. Shah; Nihar N. Patel; Andrew M. Guirgis; et al. (European Journal of Applied Physiology, 2025)

Progression and perceptual responses to blood flow restriction resistance training among people with multiple sclerosis - Ethan C. Hill; Jeffrey T. Schmidt; Kyle R. Reedy; Sean M. Lubiak; Chris E. Proppe; Paola M. Rivera; David H. Gonzalez-Rojas; John E. Lawson; Anuj J. Prajapati; Niriham M. Shah; Nihar N. Patel; Andrew M. Guirgis; et al. (European Journal of Applied Physiology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The biodiversity of ice‐free Antarctica database - Aleks Terauds; Jasmine R. Lee; Hannah S. Wauchope; Ben Raymond; Dana M. Bergstrom; Peter Convey; Claire Mason; Charlotte R. Patterson; Sharon A. Robinson; Anton Van de Putte; David Watts; Steven L. Chown (Ecology, 2025)
Antarctica is one of Earth's most untouched, inhospitable, and poorly known regions. Although knowledge of its biodiversity has increased over recent decades, a diverse, wide‐ranging, and spatially explicit compilation of the biodiversity that inhabits Antarctica's permanently ice‐free areas is unavailable. This absence hinders both Antarctic biodiversity research and the integration of Antarctica in global biodiversity–related studies. Fundamental and applied research on biodiversity patterns, ecological structure and function, and options for conservation are reliant on spatially resolved, taxonomically consistent observations. Such information is especially important for modern, data‐driven biodiversity science, in both Antarctica and globally, and forms the backbone of biodiversity informatics, reflected, for example, in the Darwin Core Standard used by the Global Biodiversity Information Facility. Biodiversity data are also essential to fulfill the conservation requirements for Antarctica, as set out in the Protocol on Environmental Protection to the Antarctic Treaty and inform the design of systematic surveys to address biodiversity and ecological knowledge gaps, for both specific taxa and ecosystems. Such surveys are key requirements for understanding and mitigating the impacts of environmental change on the region's biodiversity. Here, we address these requirements through the public release of The Biodiversity of Ice‐free Antarctica Database. In 2008, we extracted a subset of biodiversity records only from terrestrial ice‐free areas from the Scientific Committee on Antarctic Research (SCAR) Antarctic Biodiversity Database. We have subsequently added thousands of records from a range of sources: checking, and where necessary (and possible), correcting the spatial location, clarifying, cross‐referencing, and harmonizing taxonomy with globally recognized sources, and documenting the original source of records. The Biodiversity of Ice‐free Antarctica Database spans the early 1800s to 2019 (with most records collected after 1950) and represents the most comprehensive consolidation of Antarctic ice‐free biodiversity occurrence data yet compiled into a single database. The Biodiversity of Ice‐free Antarctica Database contains 35,654 records of 1890 species in over 800 genera across six kingdoms and spans all Antarctic Conservation Biogeographic Regions. These data are released under a CC BY Attribution License ( http://creativecommons.org/licenses/by/4.0/ ).

Fisheries in flux: Bridging science and policy for climate-resilient management of US fisheries under distributional change - Jacqueline M. Vogel; Arielle Levine; Catherine Longo; Rod Fujita; Catherine L. Alves; Gemma Carroll; J. Kevin Craig; Kiley Dancy; Melissa Errend; Timothy E. Essington; Nima Farchadi; Sarah Glaser; et al. (Marine Policy, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

A comparison of the early growth and survival of lesser-known tree species for climate change adaptation in Britain - Thomas S. Ovenden; Richard L. Jinks; William L. Mason; Gary Kerr; Chris Reynolds (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Increased offspring size and reduced gestation length in an ectothermic vertebrate under a worst-case climate change scenario - David L. Hubert; Ehren J. Bentz; Robert T. Mason (Journal of Thermal Biology, 2024)

Navigating Research Challenges to Estimate Blue Carbon Benefits From Saltmarsh Restoration - Victoria G. Mason; Annette Burden; Graham Epstein; Lucy L. Jupe; Kevin A. Wood; Martin W. Skov (Global Change Biology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Breeding and management of major resistance genes to stem canker/blackleg in Brassica crops - Paula Vasquez-Teuber; Thierry Rouxel; Annaliese S. Mason; Jessica L. Soyer (Theoretical and Applied Genetics, 2024)
Blackleg (also known as Phoma or stem canker) is a major, worldwide disease of Brassica crop species, notably B. napus (rapeseed, canola), caused by the ascomycete fungus Leptosphaeria maculans . The outbreak and severity of this disease depend on environmental conditions and management practices, as well as a complex interaction between the pathogen and its hosts. Genetic resistance is a major method to control the disease (and the only control method in some parts of the world, such as continental Europe), but efficient use of genetic resistance is faced with many difficulties: (i) the scarcity of germplasm/genetic resources available, (ii) the different history of use of resistance genes in different parts of the world and the different populations of the fungus the resistance genes are exposed to, (iii) the complexity of the interactions between the plant and the pathogen that expand beyond typical gene-for-gene interactions, (iv) the incredible evolutionary potential of the pathogen and the importance of knowing the molecular processes set up by the fungus to “breakdown’ resistances, so that we may design high-throughput diagnostic tools for population surveys, and (v) the different strategies and options to build up the best resistances and to manage them so that they are durable. In this paper, we aim to provide a comprehensive overview of these different points, stressing the differences between the different continents and the current prospects to generate new and durable resistances to blackleg disease.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Genetic connectivity in the Arizona toad (Anaxyrus microscaphus): implications for conservation of a stream dwelling amphibian in the arid Southwestern United States - Sara J. Oyler-McCance; Mason J. Ryan; Brian K. Sullivan; Jennifer A. Fike; Robert S. Cornman; J. Tomasz Giermakowski; Shawna J. Zimmerman; Rachel L. Harrow; Shaula J. Hedwall; Blake R. Hossack; Ian M. Latella; Robert E. Lovich; et al. (Conservation Genetics, 2024)
The Arizona Toad ( Anaxyrus microscaphus ) is restricted to riverine corridors and adjacent uplands in the arid southwestern United States. As with numerous amphibians worldwide, populations are declining and face various known or suspected threats, from disease to habitat modification resulting from climate change. The Arizona Toad has been petitioned to be listed under the U.S. Endangered Species Act and was considered “warranted but precluded” citing the need for additional information – particularly regarding natural history (e.g., connectivity and dispersal ability). The objectives of this study were to characterize population structure and genetic diversity across the species’ range. We used reduced-representation genomic sequencing to genotype 3,601 single nucleotide polymorphisms in 99 Arizona Toads from ten drainages across its range. Multiple analytical methods revealed two distinct genetic groups bisected by the Colorado River; one in the northwestern portion of the range in southwestern Utah and eastern Nevada and the other in the southeastern portion of the range in central and eastern Arizona and New Mexico. We also found subtle substructure within both groups, particularly in central Arizona where toads at lower elevations were less connected than those at higher elevations. The northern and southern parts of the Arizona Toad range are not well connected genetically and could be managed as separate units. Further, these data could be used to identify source populations for assisted migration or translocations to support small or potentially declining populations.

“Ectomycorrhizal exploration type” could be a functional trait explaining the spatial distribution of tree symbiotic fungi as a function of forest humus forms - Khalfallah F.; Bon L.; El Mazlouzi M.; Bakker M.R.; Fanin N.; Bellanger R.; Bernier F.; De Schrijver A.; Ducatillon C.; Fotelli M.N.; Gateble G.; Gundale M.J.; et al. (Mycorrhiza, 2024)

Landscape and management influences on smallholder agroforestry yields show shifts during a climate shock - Alexandra C. Morel; Sheleme Demissie; Techane Gonfa; Zia Mehrabi; Sami Rifai; Mark A. Hirons; Tadesse Woldemariam Gole; John Mason; Constance L. McDermott; Emily Boyd; Elizabeth J.Z. Robinson; Yadvinder Malhi; et al. (Agriculture, Ecosystems & Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Global change impacts on mineral nutritional quality of cereal grains: Coordinated datasets and analyses to advance a systems-based understanding - Grace L. Miner; Catherine E. Stewart; Jorge A. Delgado; James A. Ippolito; R. Esten Mason; Scott D. Haley; Mary J. Guttieri; Elizabeth A. Ainsworth; Justin M. McGrath; Sarah J. Beebout (Field Crops Research, 2024)

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Senolytic treatment fails to improve ovarian reserve or fertility in female mice - Driele N. Garcia; Jessica D. Hense; Bianka M. Zanini; Jose V. V. Isola; Juliane B. Prosczek; Sarah Ashiqueali; Thais L. Oliveira; Jeffrey B. Mason; Ines C. Schadock; Carlos C. Barros; Michael B. Stout; Michal M. Masternak; et al. (GeroScience, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

FBH1 deficiency sensitizes cells to WEE1 inhibition by promoting mitotic catastrophe - Lucy Jennings; Heather Andrews Walters; Tyler J. McCraw; Joshua L. Turner; Jennifer M. Mason (DNA Repair, 2024)

Model transferability and predicted response of a dryland anuran to climate change in the Southwest United States - Fabio Suzart de Albuquerque; Heather L. Bateman; Mason J. Ryan; Brett Montgomery (Journal of Biogeography, 2024)
Aim We propose a combined approach to explore the model transferability and the effect of climate change on habitat suitability. Location Southwest United States. Taxon Amphibians; Anura; Bufonidae; Anaxyrus microscaphus. Methods To assess the impacts of climate change on A. microscaphus , we obtained 3162 records from the Arizona Game and Fish Department. We classified occurrence records data into six historical groups (from 1960 to 2018) and a contemporary group (from 2019 to 2022). We investigated the ability of historical data to generate accurate predictions of the species' contemporary distribution. We used species distribution modelling to compute habitat suitability values and identified spatial clusters of high suitability values (using hotspot analyses). Results We show that historical occurrences successfully predicted the contemporary distribution of A. microscaphus . We demonstrate that the geographical distribution of contemporary hotspots is strongly related to precipitation of the wettest quarter. This research provides evidence that climate change will likely affect the distribution of hotspots and the habitat suitability of A. microscaphus . Losses of 37%–48% contraction are expected at the margins of the range both in the north and south of the geographic limits. Main Conclusions We show that recent past data can be used to predict contemporary species distribution accurately. We highlight that habitat suitability values of A. microscaphus are strongly related to climate, topography and distance to streams. This study provides clear evidence of the negative impacts of climate change on habitat suitability in the Southwest United States drylands. Our approach has applied utility to managers to target survey areas, monitor habitat changes, plan for conservation mitigation measures, conserve stream flows across the species' range and inform recovery if needed. Thus, managers could use previously collected data to predict contemporary species distribution when their occurrence accurately characterizes the species' ecological niche.

Global dominance of lianas over trees is driven by forest disturbance, climate and topography - Alain Senghor K. Ngute; David S. Schoeman; Marion Pfeifer; Geertje M. F. van der Heijden; Oliver L. Phillips; Michiel van Breugel; Mason J. Campbell; Chris J. Chandler; Brian J. Enquist; Rachael V. Gallagher; Christoph Gehring; Jefferson S. Hall; et al. (Global Change Biology, 2024)
Growing evidence suggests that liana competition with trees is threatening the global carbon sink by slowing the recovery of forests following disturbance. A recent theory based on local and regional evidence further proposes that the competitive success of lianas over trees is driven by interactions between forest disturbance and climate. We present the first global assessment of liana–tree relative performance in response to forest disturbance and climate drivers. Using an unprecedented dataset, we analysed 651 vegetation samples representing 26,538 lianas and 82,802 trees from 556 unique locations worldwide, derived from 83 publications. Results show that lianas perform better relative to trees (increasing liana‐to‐tree ratio) when forests are disturbed, under warmer temperatures and lower precipitation and towards the tropical lowlands. We also found that lianas can be a critical factor hindering forest recovery in disturbed forests experiencing liana‐favourable climates, as chronosequence data show that high competitive success of lianas over trees can persist for decades following disturbances, especially when the annual mean temperature exceeds 27.8°C, precipitation is less than 1614 mm and climatic water deficit is more than 829 mm. These findings reveal that degraded tropical forests with environmental conditions favouring lianas are disproportionately more vulnerable to liana dominance and thus can potentially stall succession, with important implications for the global carbon sink, and hence should be the highest priority to consider for restoration management.

Contaminant biomonitoring augmented with a qPCR array indicates hepatic mRNA gene expression effects in wild-collected seabird embryos - Mason D. King; Geoffrey Su; Doug Crump; Amani Farhat; Vicki Marlatt; Sandi L. Lee; Tony D. Williams; John E. Elliott (Science of The Total Environment, 2023)

Coyotes eat flies at carrion - David S. Mason; Abby K. Jones; Brandon T. Barton; Mike Proctor; Stephen L. Webb; Marcus A. Lashley (Food Webs, 2023)

Blue carbon benefits from global saltmarsh restoration - Victoria G. Mason; Annette Burden; Graham Epstein; Lucy L. Jupe; Kevin A. Wood; Martin W. Skov (Global Change Biology, 2023)
Coastal saltmarshes are found globally, yet are 25%–50% reduced compared with their historical cover. Restoration is incentivised by the promise that marshes are efficient storers of ‘blue’ carbon, although the claim lacks substantiation across global contexts. We synthesised data from 431 studies to quantify the benefits of saltmarsh restoration to carbon accumulation and greenhouse gas uptake. The results showed global marshes store approximately 1.41–2.44 Pg carbon. Restored marshes had very low greenhouse gas (GHG) fluxes and rapid carbon accumulation, resulting in a mean net accumulation rate of 64.70 t CO 2 e ha −1 year −1 . Using this estimate and potential restoration rates, we find saltmarsh regeneration could result in 12.93–207.03 Mt CO 2 e accumulation per year, offsetting the equivalent of up to 0.51% global energy‐related CO 2 emissions—a substantial amount, considering marshes represent

Positive responses of breeding waders to targeted conservation advice and habitat management used to enhance existing wader conservation initiatives in Northern Ireland - Christina L. Hunt; Kendrew Colhoun; Lucy R. Mason; Gillian Gilbert; Claire Barnett; Will J. Peach (Journal for Nature Conservation, 2023)

Carnivore coexistence in Chicago: niche partitioning of coyotes and red foxes - Alyson M. Cervantes; Robert L. Schooley; Elizabeth W. Lehrer; Travis Gallo; Maximilian L. Allen; Mason Fidino; Seth B. Magle (Urban Ecosystems, 2023)
Mesopredators including coyotes ( Canis latrans ) and red foxes ( Vulpes vulpes ) often co-occur in urban environments, but how niche partitioning facilitates their coexistence remains unclear. Highly urbanized areas can be spatial refuges for smaller mesopredators (i.e., spatial human shield effect), however these species also may coexist through temporal niche partitioning. We used camera traps ( n = 110 sites) across an urbanization gradient in Chicago to examine coyote-fox interactions from 2011 to 2018. We analyzed spatial partitioning through multi-season occupancy models and structural equation modeling (SEM), and quantified temporal overlap between canids and with humans. Coyotes most often occurred in natural areas, and urbanization reduced their colonization rates and increased their extinction rates. Initial occupancy for red foxes was negatively impacted by urbanization, but their extinction rates depended on a surprising interaction between coyotes and humans. When coyotes were rare, fox extinction was related positively to human activity; but when coyotes were more common, fox extinction was related negatively to human activity. This outcome may reflect a human shield effect at a within-site scale. The SEM further supported the negative impact of urbanization on both canids, and lack of an effect of coyotes on the distribution of foxes. Diel activity of coyotes and red foxes indicated temporal niche partitioning intensified at more urbanized sites. Our results suggest the spatial human shield effect is not operating across sites in Chicago. Instead, coyotes and red foxes may share green spaces, especially in highly urbanized areas, where species coexistence is promoted by temporal niche partitioning.

Drivers of conflict and resilience in shifting transboundary fisheries - Jacqueline M. Vogel; Catherine Longo; Jessica Spijkers; Juliano Palacios-Abrantes; Julia Mason; Colette C.C. Wabnitz; William Cheung; U. Rashid Sumaila; Gordon Munro; Sarah Glaser; Johann Bell; Yongjun Tian; et al. (Marine Policy, 2023)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

P14-20: Chemical and biological assessment of a Heated Tobacco Product reveals marked reductions in aerosol toxicants and in vitro toxicity compared to a combustible cigarette - R.-D. Vasile; S.J. Pour; R. Wieczorek; E.T. Sticken; V. Troude; O. Dethloff; L. Mason; L. Simms; M. Stevenson (Toxicology Letters, 2023)

Correction to: Application of somatic embryogenesis for development of emerald ash borer-resistant white ash and green ash varietals - Scott A. Merkle; Jennifer L. Koch; A. Ryan Tull; Jessica E. Dassow; David W. Carey; Brittany F. Barnes; Mason W. M. Richins; Paul M. Montello; Kira R. Eidle; Logan T. House; Daniel A. Herms; Kamal J. K. Gandhi (New Forests, 2023)

Assessing the role of the gut microbiome in methylmercury demethylation and elimination in humans and gnotobiotic mice - Genevieve L. Coe; Ian N. Krout; Mason Munro-Ehrlich; Catherine R. Beamish; Daria Vorojeikina; Daniel R. Colman; Eric J. Boyd; Seth T. Walk; Matthew D. Rand (Archives of Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

An examination of the factors influencing the bioaccumulation of methylmercury at the base of the estuarine food web - Robert P. Mason; Kate L. Buckman; Emily A. Seelen; Vivien F. Taylor; Celia Y. Chen (Science of The Total Environment, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Chronological and reproductive aging-associated changes in resistance to oxidative stress in post-reproductive female mice - Tristin L. King; Kaden B. Underwood; Kindra K. Hansen; Michael T. Kinter; Augusto Schneider; Michal M. Masternak; Jeffrey B. Mason (GeroScience, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Application of somatic embryogenesis for development of emerald ash borer-resistant white ash and green ash varietals - Scott A. Merkle; Jennifer L. Koch; A. Ryan Tull; Jessica E. Dassow; David W. Carey; Brittany F. Barnes; Mason W. M. Richins; Paul M. Montello; Kira R. Eidle; Logan T. House; Daniel A. Herms; Kamal J.K. Gandhi (New Forests, 2023)

Closing the compliance gap in marine protected areas with human behavioural sciences - Brock J. Bergseth; Adrian Arias; Michele L. Barnes; Iain Caldwell; Amber Datta; Stefan Gelcich; Sam H. Ham; Jacqueline D. Lau; Cristina Ruano‐Chamorro; Patrick Smallhorn‐West; Damian Weekers; Jessica Zamborain‐Mason; et al. (Fish and Fisheries, 2023)
Advocates, practitioners and policy‐makers continue to use and advocate for marine protected areas (MPAs) to meet global ocean protection targets. Yet many of the worlds MPAs, and especially no‐take MPAs, are plagued by poaching and ineffective governance. Using a global dataset on coral reefs as an example, we quantify the potential ecological gains of governing MPAs to increase compliance, which we call the ‘compliance gap’. Using ecological simulations based on model posteriors of joint Bayesian hierarchical models, we demonstrate how increased compliance in no‐take MPAs could nearly double target fish biomass (91% increases in median fish biomass), and result in a 292% higher likelihood of encountering top predators. Achieving these gains and closing the compliance gap necessitates a substantial shift in approach and practice to go beyond optimizing enforcement, and towards governing for compliance. This will require engaging and integrating a broad suite of actors, principles, and practices across three key domains: (i)) harnessing social influence, (ii) integrating equity principles, and (iii) aligning incentives through market‐based instruments. Empowering and shaping communication between actor groups (e.g., between fishers, practitioners, and policy‐makers) using theoretically underpinned approaches from the behavioural sciences is one of the most essential, but often underserved aspects of governing MPAs. We therefore close by highlighting how this cross‐cutting tool could be further integrated in governance to bolster high levels of compliance in MPAs.

The beta thalassaemia trait in Jamaica - G. R. Serjeant; B. E. Serjeant; K. P. Mason; F. Gibson; R-A Gardner; L. Warren; M. Reid; M. Happich; A. E. Kulozik (Journal of Community Genetics, 2023)

Impact of Access and Benefit Sharing implementation on biological control genetic resources - Peter G. Mason; Barbara I. P. Barratt; Fernando Mc Kay; Johannette N. Klapwijk; Luciana C. Silvestri; Martin Hill; Hariet L. Hinz; Andy Sheppard; Jacques Brodeur; Marcello Diniz Vitorino; Philip Weyl; Kim A. Hoelmer (BioControl, 2023)
The third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the use of genetic resources was further developed when the Nagoya Protocol on Access and Benefit Sharing came into effect in 2014. Interpretation of how this agreement is being implemented is wide-ranging and there are implications for biological control. A survey of biological control workers indicated that while some countries have facilitated access to biological control genetic resources, requirements in other countries have impeded biological control implementation. There was consensus that benefits to provider countries should be in the form of supporting local research communities. There was also agreement that the free use and exchange of biological control genetic resources has provided benefits to the global community, including to both providers and recipients of the agents. It is recommended that consideration of the free use and exchange principal should be a key element of Access and Benefit Sharing measures for the future.

International agreement for the use and exchange of classical biological control genetic resources: a practical proposal - Peter G. Mason; Fernando Mc Kay; Luciana C. Silvestri; Martin Hill; Philip Weyl; Hariet L. Hinz; Jacques Brodeur; Marcelo Diniz Vitorino; Barbara I. P. Barratt (BioControl, 2023)
The Nagoya Protocol on Access and Benefit Sharing (ABS) was implemented to further develop the third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the utilization of genetic resources. Interpretation of this agreement is wide-ranging and there is concern that if ABS measures are poorly implemented biological control and the resultant public good will be greatly impeded. The ethos of multilateral use and exchange of genetic resources used in classical biological control will be particularly affected. In the spirit of the fair and equitable sharing of benefits arising out of the utilization of genetic resources, we propose a simple practical solution in the form of an international agreement on the use and exchange of classical biological control genetic resources.

Precessional pacing of early Proterozoic redox cycles - Margriet L. Lantink; Wytze K. Lenstra; Joshua H.F.L. Davies; Rick Hennekam; David McB. Martin; Paul R.D. Mason; Gert-Jan Reichart; Caroline P. Slomp; Frederik J. Hilgen (Earth and Planetary Science Letters, 2023)

Analyzing mobility trends of tracked vehicles on fine-grained soils in a progressive slip condition using full-scale test data presented in DROVE 3.0 - Arman Borazjani; Isaac L. Howard; Zach Griffing; Ashley S. Carey; Farshid Vahedifard; George L. Mason; Jody D. Priddy (Journal of Terramechanics, 2023)

Flexible and open-source programs for quantitative image analysis in microbial ecology - Alexis L. Pasulka; Jonathan F. Hood; Dana E. Michels; Mason D. Wright (Frontiers in Marine Science, 2023)
Epifluorescence microscopy is an essential tool for obtaining reliable estimates of the abundance of marine microorganisms including viruses. However, computational analysis is required to gain consistent and quantitative data from digital microscopy images. Many imaging programs are proprietary and cost-prohibitive. The currently available free imaging programs are often platform specific and/or lack the flexibility to analyze microscopy images from natural samples, such as the planktonic environment, which can contain challenges such as debris and high background signals. Here we describe two MATLAB-based open-source image analysis programs that work across computer platforms and provide the tools to analyze a range of image types and cell sizes with a user-friendly interface. The Microbial Image Analysis (MiA) program aims to provide flexibility for the selection, identification, and quantification of cells that vary in size and fluorescence intensity within natural microbial communities. The Viral Image Analysis (ViA) program aims to provide an effective means for quantifying viral abundances from epifluorescence images as well as enumerating the intensity of a primary and secondary stain. In this paper, we provide an overview of the functionality of the MiA and ViA programs and highlight specific program features through several microbial image case studies.

Predicting COVID-19 cases using SARS-CoV-2 RNA in air, surface swab and wastewater samples - Helena M. Solo-Gabriele; Shelja Kumar; Samantha Abelson; Johnathon Penso; Julio Contreras; Kristina M. Babler; Mark E. Sharkey; Alejandro M.A. Mantero; Walter E. Lamar; John J. Tallon; Erin Kobetz; Natasha Schaefer Solle; et al. (Science of The Total Environment, 2023)

GH deficiency confers protective advantages against Alzheimer’s disease through rescued miRNA expression profile in APP/PS1 mice - Sarah Noureddine; Tatiana Saccon; Trina Rudeski-Rohr; Adam Gesing; Jeffrey B. Mason; Augusto Schneider; Joseph Dhabhi; Kendra L. Puig; Sharlene Rakoczy; Holly M. Brown-Borg; Michal M. Masternak (GeroScience, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Defining and analyzing health system resilience in rural jurisdictions - Mason Barnard; Sienna Mark; Scott L. Greer; Benjamin D. Trump; Igor Linkov; Holly Jarman (Environment Systems and Decisions, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Aging-associated changes in motor function are ovarian somatic tissue-dependent, but germ cell and estradiol independent in post-reproductive female mice exposed to young ovarian tissue - Tracy L. Habermehl; Kaden B. Underwood; Kevin D. Welch; Steven P. Gawrys; Kate C. Parkinson; Augusto Schneider; Michal M. Masternak; Jeffrey B. Mason (GeroScience, 2022)

Managing fisheries for maximum nutrient yield - James P.W. Robinson; Kirsty L. Nash; Julia L. Blanchard; Nis S. Jacobsen; Eva Maire; Nicholas A.J. Graham; M. Aaron MacNeil; Jessica Zamborain‐Mason; Edward H. Allison; Christina C. Hicks (Fish and Fisheries, 2022)
Wild‐caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutrition‐sensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation for managing fisheries for multispecies Maximum Nutrient Yield (mMNY). We empirically test our approach using size‐based models of North Sea and Baltic Sea fisheries and show that mMNY is predicted by the relative contribution of nutritious species to total catch and their vulnerability to fishing, leading to trade‐offs between catch and specific nutrients. Simulated nutrient yield curves suggest that vitamin D, which is deficient in Northern European diets, was underfished at fishing levels that returned maximum catch weights. Analysis of global catch data shows there is scope for nutrient yields from most of the world's marine fisheries to be enhanced through nutrient‐sensitive fisheries management. With nutrient composition data now widely available, we expect our mMNY framework to motivate development of nutrient‐based reference points in specific contexts, such as data‐limited fisheries. Managing for mMNY alongside policies that promote access to fish could help close nutrient gaps for coastal populations, maximising the contribution of wild‐caught fish to global food and nutrition security.

The use patterns of novel psychedelics: experiential fingerprints of substituted phenethylamines, tryptamines and lysergamides - P. Mallaroni; N. L. Mason; F. R. J. Vinckenbosch; J. G. Ramaekers (Psychopharmacology, 2022)
Background Novel psychedelics (NPs) are an expanding set of compounds, presenting new challenges for drug policy and opportunities for clinical research. Unlike their classical derivatives, little is known regarding their use profiles or their subjective effects. Aims The purpose of this study was to compile usage patterns and adverse event rates for individual NPs belonging to each of three main psychedelic structural families. Targeting the most widely used representatives for each class, we expanded on their phenomenological distinctions. Methods A two-part survey was employed. We investigated the prevalence of novel phenethylamines, tryptamine and lysergamides in NP users ( N = 1180), contrasting the type and incidence of adverse events (AEs) using a set of logistic regressions. Honing in on 2–4-Bromo-2,5-dimethoxyphenyl)ethanamine (2C-B) (48.6%), 1-propionyl-lysergic acid diethylamide (1P-LSD) (34.2%) and 4-Acetoxy-N,N-dimethyltryptamine (4-AcO-DMT) (23.1%), we examined their phenomenological separability using a gradient boosting (XGBoost) supervised classifier. Results Novel phenethylamines had the highest prevalence of use (61.5%) seconded by tryptamines (43.8%) and lysergamides (42.9%). Usage patterns were identified for 32 different compounds, demonstrating variable dosages, durations and a common oral route of administration. Compared to phenethylamines, the odds for tryptamines and lysergamides users were significantly less for overall physical AEs. No significant differences in overall psychological AEs were found. Overall model area under the curve (AUC) stood at 0.79 with sensitivity (50.0%) and specificity (60.0%) for 2C-B ranking lowest. Conclusion NP classes may hold distinct AE rates and phenomenology, the latter potentially clouded by the subjective nature of these experiences. Further targeted research is warranted.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The haematology of Jamaicans: red cell indices in HbAA, HbAS, HbAC, and HbA-HPFH genotypes - G. R. Serjeant; B. E. Serjeant; K. P. Mason; F. Gibson; C. Osmond; S. L. Thein; M. Happich; A. E. Kulozik (Journal of Community Genetics, 2022)

Fast but steady: An integrated leaf‐stem‐root trait syndrome for woody forest invaders - Jason D. Fridley; Taryn L. Bauerle; Alaä Craddock; Alex R. Ebert; Douglas A. Frank; J. Mason Heberling; Elise D. Hinman; Insu Jo; Kelsey A. Martinez; Maria S. Smith; Lauren J. Woolhiser; Jingjing Yin (Ecology Letters, 2022)
Successful control and prevention of biological invasions depend on identifying traits of non‐native species that promote fitness advantages in competition with native species. Here, we show that, among 76 native and non‐native woody plants of deciduous forests of North America, invaders express a unique functional syndrome that combines high metabolic rate with robust leaves of longer lifespan and a greater duration of annual carbon gain, behaviours enabled by seasonally plastic xylem structure and rapid production of thin roots. This trait combination was absent in all native species examined and suggests the success of forest invaders is driven by a novel resource‐use strategy. Furthermore, two traits alone—annual leaf duration and nuclear DNA content—separated native and invasive species with 93% accuracy, supporting the use of functional traits in invader risk assessments. A trait syndrome reflecting both fast growth capacity and understorey persistence may be a key driver of forest invasions.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Differential and interacting impacts of invasive plants and white-tailed deer in eastern U.S. forests - David L. Gorchov; Bernd Blossey; Kristine M. Averill; Andrea Dávalos; J. Mason Heberling; Michael A. Jenkins; Susan Kalisz; William J. McShea; Janet A. Morrison; Victoria Nuzzo; Christopher R. Webster; Donald M. Waller (Biological Invasions, 2021)

A placebo-controlled study of the effects of ayahuasca, set and setting on mental health of participants in ayahuasca group retreats - M. V. Uthaug; N. L. Mason; S. W. Toennes; J. T. Reckweg; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; K. van Oorsouw; J. Riba; J. G. Ramaekers (Psychopharmacology, 2021)
Ayahuasca is a plant concoction containing N,N -dimethyltryptamine (DMT) and certain β-carboline alkaloids from South America. Previous research in naturalistic settings has suggested that ingestion of ayahuasca can improve mental health and well-being; however, these studies were not placebo controlled and did not control for the possibility of expectation bias. This naturalistic observational study was designed to assess whether mental health changes were produced by ayahuasca or by set and setting. Assessments were made pre- and post-ayahuasca sessions in 30 experienced participants of ayahuasca retreats hosted in the Netherlands, Spain, and Germany. Participants consumed ayahuasca ( N = 14) or placebo ( N = 16). Analysis revealed a main effect of time on symptoms of depression, anxiety, and stress. Compared to baseline, symptoms reduced in both groups after the ceremony, independent of treatment. There was a main treatment × time interaction on implicit emotional empathy, indicating that ayahuasca increased emotional empathy to negative stimuli. The current findings suggest that improvements in mental health of participants of ayahuasca ceremonies can be driven by non-pharmacological factors that constitute a placebo response but also by pharmacological factors that are related to the use of ayahuasca. These findings stress the importance of placebo-controlled designs in psychedelic research and the need to further explore the contribution of non-pharmacological factors to the psychedelic experience.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Correction to: Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

Salicinoid phenolics reduce adult Anoplophora glabripennis (Cerambicidae: Lamiinae) feeding and egg production - Charles J. Mason; Kennedy Rubert-Nason; Richard L. Lindroth; Juan Shi; Kelli Hoover (Arthropod-Plant Interactions, 2021)

Physiological responses during simulated 16 km recumbent handcycling time trial and determinants of performance in trained handcyclists - Benjamin Stone; Barry S. Mason; Ben T. Stephenson; Vicky L. Goosey-Tolfrey (European Journal of Applied Physiology, 2020)
Purpose To characterise the physiological profiles of trained handcyclists, during recumbent handcycling, to describe the physiological responses during a 16 km time trial (TT) and to identify the determinants of this TT performance. Methods Eleven male handcyclists performed a sub-maximal and maximal incremental exercise test in their recumbent handbike, attached to a Cyclus II ergometer. A physiological profile, including peak aerobic power output (PO Peak ), peak rate of oxygen uptake ( $$\dot{V}$$ V ˙ O 2Peak ), aerobic lactate threshold (AeLT) and PO at 4 mmol L −1 (PO 4 ), were determined. Participants also completed a 16 km simulated TT using the same experimental set-up. Determinants of TT performance were identified using stepwise multiple linear regression analysis. Results Mean values of PO Peak = 252 ± 9 W, $$\dot{V}$$ V ˙ O 2Peak = 3.30 ± 0.36 L min −1 (47.0 ± 6.8 mL kg −1 min −1 ), AeLT = 87 ± 13 W and PO 4 = 154 ± 14 W were recorded. The TT was completed in 29:21 ± 0:59 min:s at an intensity equivalent to 69 ± 4% PO Peak and 87 ± 5% $$\dot{V}$$ V ˙ O 2Peak . PO Peak ( r = − 0.77, P = 0.006), PO 4 ( r = − 0.77, P = 0.006) and AeLT ( r = − 0.68, P = 0.022) were significantly correlated with TT performance. PO 4 and PO Peak were identified as the best predictors of TT performance ( r = 0.89, P < 0.001). Conclusion PO Peak , PO 4 and AeLT are important physiological TT performance determinants in trained handcyclists, differentiating between superior and inferior performance, whereas $$\dot{V}$$ V ˙ O 2peak was not. The TT took place at an intensity corresponding to 69% PO Peak and 87% $$\dot{V}$$ V ˙ O 2peak .

Cytogenetics of Fraxinus mandshurica and F. quadrangulata: ploidy determination and rDNA analysis - Nurul Islam-Faridi; Mary E. Mason; Jennifer L. Koch; C. Dana Nelson (Tree Genetics & Genomes, 2020)
Ashes ( Fraxinus spp. ) are important hardwood tree species in rural, suburban, and urban forests of the eastern USA. Unfortunately, emerald ash borer (EAB, Agrilus planipennis ) an invasive insect pest that was accidentally imported from Asia in the late 1980s–early 1990s is destroying them at an alarming rate. All North American ashes are highly susceptible to EAB, although blue ash ( F. quadrangulata ) may have some inherent attributes that provide it some protection. In contrast Manchurian ash ( F. mandshurica ) is relatively resistant to EAB having coevolved with the insect pest in its native range in Asia. Given its level of resistance, Manchurian ash has been considered for use in interspecies breeding programs designed to transfer resistance to susceptible North American ash species. One prerequisite for successful interspecies breeding is consistency in chromosome ploidy level and number between the candidate species. In the current study, we cytologically determined that both Manchurian ash and blue ash are diploids (2 n ) and have the same number of chromosomes (2 n = 2 x = 46). We also characterized these species’ ribosomal gene families (45S and 5S rDNA) using fluorescence in situ hybridization (FISH). Both Manchurian and blue ash showed two 45S rDNA and one 5S rDNA sites, but blue ash appears to have an additional site of 45S rDNA. The 5S rDNA in both species is colocalized interstitially with one of the 45S rDNA sites. The copy number of these two ribosomal gene families in Manchurian ash were observed to be quite varied, which indicates the species are still undergoing evolutionary homogenization.

Mismatched outcomes for biodiversity and ecosystem services: testing the responses of crop pollinators and wild bee biodiversity to habitat enhancement - Charlie C. Nicholson; Kimiora L. Ward; Neal M. Williams; Rufus Isaacs; Keith S. Mason; Julianna K. Wilson; Julia Brokaw; Larry J. Gut; Nikki L. Rothwell; Thomas J. Wood; Sujaya Rao; George D. Hoffman; et al. (Ecology Letters, 2020)
Supporting ecosystem services and conserving biodiversity may be compatible goals, but there is concern that service‐focused interventions mostly benefit a few common species. We use a spatially replicated, multiyear experiment in four agricultural settings to test if enhancing habitat adjacent to crops increases wild bee diversity and abundance on and off crops. We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and compositionally different bee communities compared to control edges. Enhancements did not increase the abundance or diversity of bees visiting crops, indicating that the supply of pollination services was unchanged following enhancement. We find that actions to promote crop pollination improve multiple dimensions of biodiversity, underscoring their conservation value, but these benefits may not be spilling over to crops. More work is needed to identify the conditions that promote effective co‐management of biodiversity and ecosystem services.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Genetic, spatial, and temporal aspects of decline and mortality in a Fraxinus provenance test following invasion by the emerald ash borer - Kim C. Steiner; Lake E. Graboski; Kathleen S. Knight; Jennifer L. Koch; Mary E. Mason (Biological Invasions, 2019)

Non-dairy probiotic food products: An emerging group of functional foods - Min Min; Craig R. Bunt; Susan L. Mason; Malik A. Hussain (Critical Reviews in Food Science and Nutrition, 2019)

Health sequelae of human cryptosporidiosis—a 12-month prospective follow-up study - B. L. Carter; R. E. Stiff; K. Elwin; H. A. Hutchings; B. W. Mason; A. P. Davies; R. M. Chalmers (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Boreal Forest Floor Greenhouse Gas Emissions Across a Pleurozium schreberi-Dominated, Wildfire-Disturbed Chronosequence - Kelly E. Mason; Simon Oakley; Lorna E. Street; María Arróniz-Crespo; David L. Jones; Thomas H. DeLuca; Nicholas J. Ostle (Ecosystems, 2019)

Carbon dynamics, net primary productivity and human‐appropriated net primary productivity across a forest–cocoa farm landscape in West Africa - Alexandra C. Morel; Michael Adu Sasu; Stephen Adu‐Bredu; Marvin Quaye; Christine Moore; Rebecca Ashley Asare; John Mason; Mark Hirons; Constance L. McDermott; Elizabeth J. Z. Robinson; Emily Boyd; Ken Norris; et al. (Global Change Biology, 2019)
Terrestrial net primary productivity ( NPP ) is an important metric of ecosystem functioning; however, there are little empirical data on the NPP of human‐modified ecosystems, particularly smallholder, perennial crops like cocoa ( Theobroma cacao ), which are extensive across the tropics. Human‐appropriated NPP ( HANPP ) is a measure of the proportion of a natural system's NPP that has either been reduced through land‐use change or harvested directly and, previously, has been calculated to estimate the scale of the human impact on the biosphere. Additionally, human modification can create shifts in NPP allocation and decomposition, with concomitant impacts on the carbon cycle. This study presents the results of 3 years of intensive monitoring of forest and smallholder cocoa farms across disturbance, management intensity, distance from forest and farm age gradients. We measured among the highest reported NPP values in tropical forest, 17.57 ± 2.1 and 17.7 ± 1.6 Mg C ha −1 year −1 for intact and logged forest, respectively; however, the average NPP of cocoa farms was still higher, 18.8 ± 2.5 Mg C ha −1 year −1 , which we found was driven by cocoa pod production. We found a dramatic shift in litterfall residence times, where cocoa leaves decomposed more slowly than forest leaves and shade tree litterfall decomposed considerably faster, indicating significant changes in rates of nutrient cycling. The average HANPP value for all cocoa farms was 2.1 ± 1.1 Mg C ha −1 year −1 ; however, depending on the density of shade trees, it ranged from −4.6 to 5.2 Mg C ha −1 year −1 . Therefore, rather than being related to cocoa yield, HANPP was reduced by maintaining higher shade levels. Across our monitored farms, 18.9% of farm NPP was harvested (i.e., whole cocoa pods) and only 1.1% (i.e., cocoa beans) was removed from the system, suggesting that the scale of HANPP in smallholder cocoa agroforestry systems is relatively small.

Current and future prospects for the use of pulsed electric field in the meat industry - Zuhaib F. Bhat; James D. Morton; Susan L. Mason; Alaa El-Din A. Bekhit (Critical Reviews in Food Science and Nutrition, 2019)

Cover - Andrew J. Mason; Felipe G. Grazziotin; Hussam Zaher; Alan R. Lemmon; Emily Moriarty Lemmon; Christopher L. Parkinson (Journal of Biogeography, 2019)

Reticulate evolution in nuclear Middle America causes discordance in the phylogeny of palm‐pitvipers (Viperidae: Bothriechis ) - Andrew J. Mason; Felipe G. Grazziotin; Hussam Zaher; Alan R. Lemmon; Emily Moriarty Lemmon; Christopher L. Parkinson (Journal of Biogeography, 2019)
Aim A number of processes can lead to weak or conflicting phylogenetic signals, especially in geographically dynamic regions where unstable landscapes and climates promote complex evolutionary histories. The Middle American pitviper genus Bothriechis has a complex biogeographic distribution and previous phylogenetic analyses have recovered conflicting topologies based on the data type used. Here, we tested whether historic conflicts in the phylogeny were the result of reticulate evolution and whether the inferred biogeographic history of the group would enable contact among reticulate lineages. Location Middle America. Taxon Palm‐pitvipers (genus Bothriechis ). Methods We generated a phylogenomic dataset using an anchored phylogenomics approach and inferred a genomics‐based species tree and mitochondrial tree to assess incongruence among datasets. We then generated a dated phylogeny and conducted ancestral area reconstruction to examine the biogeographic history surrounding the diversification of these species. We additionally tested whether the discordance among trees is better explained by lineage sorting or reticulate evolution by testing models of reticulate evolution inferred through multiple methods. Results We found strong support for discordance in the phylogeny of Bothriechis and corresponding evidence for reticulate evolution among lineages with incongruent placement. Ancestral area reconstruction placed these taxa in adjacent regions during the time period when reticulation was projected to take place and suggested a biogeographic history heavily influenced by vicariant processes. Main conclusions Reticulation among geographically proximate lineages has driven apparent genomic discordance in Bothriechis and is responsible for historical incongruence in the phylogeny. Inference of the order of events suggests that reticulation among nuclear Middle American taxa occurred during a time of geologic upheaval, promoting lineage divergence and secondary contact. Reticulate evolution and similar processes can have substantial impacts on the evolutionary trajectory of taxa and are important to explicitly test for in biogeographically complex regions.

Extension of longevity and reduction of inflammation is ovarian-dependent, but germ cell-independent in post-reproductive female mice - Tracy L. Habermehl; Kate C. Parkinson; Gene B. Hubbard; Yuji Ikeno; Jennifer I. Engelmeyer; Björn Schumacher; Jeffrey B. Mason (GeroScience, 2019)

Substrate-Borne Vibration Mediates Intrasexual Agonism in the New Zealand Cook Strait Giant Weta (Deinacrida rugosa) - Daniel R. Howard; Ashley P. Schmidt; Carrie L. Hall; Andrew C. Mason (Journal of Insect Behavior, 2018)

Sub-acute and long-term effects of ayahuasca on affect and cognitive thinking style and their association with ego dissolution - M. V. Uthaug; K. van Oorsouw; K. P. C. Kuypers; M. van Boxtel; N. J. Broers; N. L. Mason; S. W. Toennes; J. Riba; J. G. Ramaekers (Psychopharmacology, 2018)

Comparison of the pharmacokinetics of plant-based treatments in milk and plasma of USDA organic dairy cattle with and without mastitis - Sharon E Mason; Keena A. E. Mullen; Steven P. Washburn; Kevin L. Anderson; Ronald E. Baynes (Food Additives & Contaminants: Part A, 2018)

Drug liking and wanting, not impulsive action or reflection is increased by 4-fluoroamphetamine - K. P. C. Kuypers; E. B. de Sousa Fernandes Perna; P. C. Dolder; S. W. Toennes; E. L. Theunissen; N. L. Mason; N. R. P. W. Hutten; J. G. Ramaekers (Psychopharmacology, 2018)

An assessment of nutrients and sedimentation in the St. Thomas East End Reserves, US Virgin Islands - Anthony S. Pait; Francis R. Galdo; S. Ian Hartwell; Dennis A. Apeti; Andrew L. Mason (Environmental Monitoring and Assessment, 2018)

Correction to: Incorporating pleiotropic quantitative trait loci in dissection of complex traits: seed yield in rapeseed as an example - Ziliang Luo; Meng Wang; Yan Long; Yongju Huang; Lei Shi; Chunyu Zhang; Xiang Liu; Bruce D. L. Fitt; Jinxia Xiang; Annaliese S. Mason; Rod J. Snowdon; Peifa Liu; et al. (Theoretical and Applied Genetics, 2018)

Incorporating pleiotropic quantitative trait loci in dissection of complex traits: seed yield in rapeseed as an example - Ziliang Luo; Meng Wang; Yan Long; Yongju Huang; Lei Shi; Chunyu Zhang; Xiang Liu; Bruce D. L. Fitt; Jinxia Xiang; Annaliese S. Mason; Rod J. Snowdon; Peifa Liu; et al. (Theoretical and Applied Genetics, 2017)
Key message A comprehensive linkage atlas for seed yield in rapeseed. Abstract Most agronomic traits of interest for crop improvement (including seed yield) are highly complex quantitative traits controlled by numerous genetic loci, which brings challenges for comprehensively capturing associated markers/genes. We propose that multiple trait interactions underlie complex traits such as seed yield, and that considering these component traits and their interactions can dissect individual quantitative trait loci (QTL) effects more effectively and improve yield predictions. Using a segregating rapeseed ( Brassica napus ) population, we analyzed a large set of trait data generated in 19 independent experiments to investigate correlations between seed yield and other complex traits, and further identified QTL in this population with a SNP-based genetic bin map. A total of 1904 consensus QTL accounting for 22 traits, including 80 QTL directly affecting seed yield, were anchored to the B. napus reference sequence. Through trait association analysis and QTL meta-analysis, we identified a total of 525 indivisible QTL that either directly or indirectly contributed to seed yield, of which 295 QTL were detected across multiple environments. A majority (81.5%) of the 525 QTL were pleiotropic. By considering associations between traits, we identified 25 yield-related QTL previously ignored due to contrasting genetic effects, as well as 31 QTL with minor complementary effects. Implementation of the 525 QTL in genomic prediction models improved seed yield prediction accuracy. Dissecting the genetic and phenotypic interrelationships underlying complex quantitative traits using this method will provide valuable insights for genomics-based crop improvement.

Pyramid Screening: Combining Three Genetic Screens into One Efficient Screen for Shoot Regeneration Mutants in Arabidopsis thaliana - May Quach Mason; Travis L. Goron; Ewa Dziewiecka Arnold; Patricia Dickinson; Arani Kajenthira; Stephen J. Dinka; Rosalinda Oro; Manish N. Raizada (Journal of Plant Growth Regulation, 2017)

Loss of developmental pluripotency occurs in two stages during leaf aging in Arabidopsis thaliana - Manish N. Raizada; Travis L. Goron; Ovik Bannerjee; May Quach Mason; Michael Pautler; Jan Brazolot; Adam D. Morris; Arani Kajenthira; Stephen J. Dinka; Natalie DiMeo (In Vitro Cellular & Developmental Biology - Plant, 2017)

Revealing pMDI Spray Initial Conditions: Flashing, Atomisation and the Effect of Ethanol - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2017)

Voluntary premarital screening to prevent sickle cell disease in Jamaica: does it work? - G. R. Serjeant; B. E. Serjeant; K. P. Mason; F. Gibson; R. Gardner; L. Warren; M. Jonker (Journal of Community Genetics, 2017)

Crop health and its global impacts on the components of food security - S. Savary; S. Bregaglio; L. Willocquet; D. Gustafson; D. Mason D’Croz; A. Sparks; N. Castilla; A. Djurle; C. Allinne; Mamta Sharma; V. Rossi; L. Amorim; et al. (Food Security, 2017)

Pharmacokinetic analysis of thymol, carvacrol and diallyl disulfide after intramammary and topical applications in healthy organic dairy cattle - Sharon E. Mason; Keena A. E. Mullen; Kevin L. Anderson; Steven P. Washburn; James L. Yeatts; Ronald E. Baynes (Food Additives & Contaminants: Part A, 2017)

Studying interactions between excavating sponges and massive corals by the use of hybrid cores - James K. H. Fang; Robert A. B. Mason; Christine H. L. Schönberg; Ove Hoegh‐Guldberg; Sophie Dove (Marine Ecology, 2017)
Excavating sponges often compete with reef‐building corals. To study sponge–coral interactions, we devised a design of hybrid cores that allows sponges and corals to be arranged side by side with similar size and shape, mimicking the situation of neighbouring organisms. Compared to earlier methods that attached sponge cores onto coral surfaces, hybrid cores provide an opportunity to study organism interactions under conditions more equal to the interacting partners. The use of hybrid cores was demonstrated for the excavating sponge Cliona orientalis and the massive coral Porites , which commonly interact on the Great Barrier Reef. Cliona orientalis and massive Porites were cut into half‐moon shaped explants and combined as hybrid cores under replicate conditions. After 90 days in an aquarium setting, positive growth of Cl. orientalis along with net bioerosion were observed in sponge control cores that combined Cl. orientalis with blank substrate. However, when Cl. orientalis and massive Porites were in contact in interaction cores, the sponge displayed negative growth and undetectable bioerosion, and was slightly overgrown by the coral. Cliona orientalis may have developed tissue extension beneath the living coral tissue, but growth and net calcification rates of massive Porites were apparently not affected by Cl. orientalis when comparing the interaction cores to coral control cores that combined massive Porites with blank substrate. Overall, the present work demonstrated that hybrid cores can be used to generate conditions suitable for studying sponge–coral interactions in the laboratory, which can also be applied in the field.

Newborn screening for sickle cell disease in Jamaica: logistics and experience with umbilical cord samples - G. R. Serjeant; B. E. Serjeant; K. P. Mason; R. Gardner; L. Warren; F. Gibson; M. Coombs (Journal of Community Genetics, 2017)

Long‐term climate and competition explain forest mortality patterns under extreme drought - Derek J. N. Young; Jens T. Stevens; J. Mason Earles; Jeffrey Moore; Adam Ellis; Amy L. Jirka; Andrew M. Latimer (Ecology Letters, 2017)
Rising temperatures are amplifying drought‐induced stress and mortality in forests globally. It remains uncertain, however, whether tree mortality across drought‐stricken landscapes will be concentrated in particular climatic and competitive environments. We investigated the effects of long‐term average climate [i.e. 35‐year mean annual climatic water deficit (CWD)] and competition (i.e. tree basal area) on tree mortality patterns, using extensive aerial mortality surveys conducted throughout the forests of California during a 4‐year statewide extreme drought lasting from 2012 to 2015. During this period, tree mortality increased by an order of magnitude, typically from tens to hundreds of dead trees per km 2 , rising dramatically during the fourth year of drought. Mortality rates increased independently with average CWD and with basal area, and they increased disproportionately in areas that were both dry and dense. These results can assist forest managers and policy‐makers in identifying the most drought‐vulnerable forests across broad geographic areas.

Developmental morphology of a lyriform organ in the Western black widow (Latrodectus hesperus) - Erica L. Morley; Senthurran Sivalinghem; Andrew C. Mason (Zoomorphology, 2016)

HyLogger-3, a visible to shortwave and thermal infrared reflectance spectrometer system for drill core logging: functional description - M. C. Schodlok; L. Whitbourn; J. Huntington; P. Mason; A. Green; M. Berman; D. Coward; P. Connor; W. Wright; M. Jolivet; R. Martinez (Australian Journal of Earth Sciences, 2016)

An assessment of butyltins and metals in sediment cores from the St. Thomas East End Reserves, USVI - S. Ian Hartwell; Dennis A. Apeti; Andrew L. Mason; Anthony S. Pait (Environmental Monitoring and Assessment, 2016)

Varicella zoster virus infection of human fetal lung cells alters mitochondrial morphology - Amy C. Keller; Hussain Badani; P. Mason McClatchey; Nicholas L. Baird; Jacqueline L. Bowlin; Ron Bouchard; Guey-Chuen Perng; Jane E. B. Reusch; Benedikt B. Kaufer; Don Gilden; Aamir Shahzad; Peter G. E. Kennedy; et al. (Journal of NeuroVirology, 2016)

Behavioral and morphological responses of an insect herbivore to low nutrient quality are inhibited by plant chemical defenses - J. J. Couture; C. J. Mason; C. W. Habeck; R. L. Lindroth (Arthropod-Plant Interactions, 2016)

Testing for functional convergence of temperate rainforest tree assemblages in Chile and New Zealand - CH Lusk; M Jimenez‐Castillo; R Aragón; TA Easdale; L Poorter; LF Hinojosa; NWH Mason (New Zealand Journal of Botany, 2016)
An important tenet of biogeography and comparative ecology is that disjunct assemblages in similar physical environments are functionally more similar to each other than to assemblages from other environments. Temperate rainforests in South America, New Zealand and Australia share certain physiognomic similarities, but we are not aware of any statistical evidence that these disjunct plant assemblages share a distinctive suite of functional traits, or trait combinations. We compiled height, leaf, wood and reproductive traits from the 25 commonest arborescent species at Chilean and New Zealand sites matched for summer rainfall, summer maximum temperatures, and winter minimum temperatures. We then used multivariate tests of trait convergence. Tropical and subtropical assemblages served as out‐groups. PERMANOVA showed convergence of trait centroids at the two temperate sites, where trees on average had denser wood and smaller leaves than trees at the (sub)tropical sites. Principal components analyses carried out separately on each assemblage showed that the Chilean and New Zealand assemblages were also the most similar pair in terms of trait relationships, although New Zealand also shared strong similarities with subtropical Argentina. The main axis of variation in both temperate assemblages ranged from small, short‐lived understorey trees with soft leaves, to emergents with sclerophyllous leaves and fairly dense wood. However, the New Zealand assemblage was much richer in small trees with soft leaves than its Chilean counterpart; possible historical influences on this difference include conditions favouring radiation of small trees during the late Neogene in New Zealand, competition from Chusquea bamboos in Chile and the historical absence of browsing mammals from New Zealand. Environmental filtering has produced similar values of individual traits in Chile and New Zealand, but only partial convergence of functional trait combinations. As far as we know, this is the first study to statistically test whether disjunct tree assemblages on climatically matched sites are more functionally similar to each other than to assemblages from other environments.

Insights into Spray Development from Metered-Dose Inhalers Through Quantitative X-ray Radiography - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Peter J. Stewart; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Julio Soria; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Temporally and Spatially Resolved x-ray Fluorescence Measurements of in-situ Drug Concentration in Metered-Dose Inhaler Sprays - Daniel J. Duke; Alan L. Kastengren; Nicholas Mason-Smith; Yang Chen; Paul M. Young; Daniela Traini; David Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Interactions between Bacteria And Aspen Defense Chemicals at the Phyllosphere – Herbivore Interface - Charles J. Mason; Tiffany M. Lowe-Power; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Connectivity mapping uncovers small molecules that modulate neurodegeneration in Huntington’s disease models - Joshua L. Smalley; Carlo Breda; Robert P. Mason; Gurdeep Kooner; Ruth Luthi-Carter; Timothy W. Gant; Flaviano Giorgini (Journal of Molecular Medicine, 2016)

Active auditory mechanics in female black-horned tree crickets (Oecanthus nigricornis) - Erica L. Morley; Andrew C. Mason (Journal of Comparative Physiology A, 2015)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

A comparison of the 31 January–1 February 1953 and 5–6 December 2013 coastal flood events around the UK - Matthew P. Wadey; Ivan. D. Haigh; Robert J. Nicholls; Jennifer M. Brown; Kevin Horsburgh; Ben Carroll; Shari L. Gallop; Travis Mason; Elizabeth Bradshaw (Frontiers in Marine Science, 2015)

Intraspecific variation in Fraxinus pennsylvanica responses to emerald ash borer (Agrilus planipennis) - J. L. Koch; D. W. Carey; M. E. Mason; T. M. Poland; K. S. Knight (New Forests, 2015)

Methane and microbial dynamics in the Gulf of Mexico water column - Chrisoulla V. Rakowski; Cedric Magen; Samantha Bosman; Kelsey L. Rogers; Lauren E. Gillies; Jeffrey P. Chanton; Olivia U. Mason (Frontiers in Marine Science, 2015)

Contrasting Patterns of Diterpene Acid Induction by Red Pine and White Spruce to Simulated Bark Beetle Attack, and Interspecific Differences in Sensitivity Among Fungal Associates - Charles J. Mason; Kier D. Klepzig; Brian J. Kopper; Philip J. Kersten; Barbara L. Illman; Kenneth F. Raffa (Journal of Chemical Ecology, 2015)

Marking by elytral clip changes stridulatory characteristics and reduces reproduction in the American burying beetle, Nicrophorus americanus - Carrie L. Hall; Daniel R. Howard; Rosemary J. Smith; Andrew C. Mason (Journal of Insect Conservation, 2015)

Aspen Defense Chemicals Influence Midgut Bacterial Community Composition of Gypsy Moth - Charles J. Mason; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2015)

Apparent environmental synergism drives the dynamics of Amazonian forest fragments - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Mason Campbell; Philip M. Fearnside; Will Edwards; Jefferson J. Valsko; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Many contemporary ecosystems are likely to be affected by multiple environmental drivers, complicating efforts to predict future changes in those ecosystems. We studied long‐term changes (1980–2012) in forest dynamics and liana (woody vine) abundance and biomass in fragmented and intact forests of the central Amazon. We did so by contrasting trends in 33 permanent 1‐ha plots near forest edges (plot center 2 or regional climate drivers that influence forest dynamics. Hence, the dynamics of Amazonian forest fragments cannot be understood simply as a consequence of forest fragmentation. Rather, the changes we observed appear to arise from an interaction of fragmentation with one or more global‐ or regional‐scale drivers affecting forest dynamics. Both sets of phenomena are evidently increasing forest dynamics and liana abundances in fragmented forests, changes that could reduce carbon storage and alter many aspects of forest ecology.

An assessment of chemical contaminants in sediments from the St. Thomas East End Reserves, St. Thomas, USVI - Anthony S. Pait; S. Ian Hartwell; Andrew L. Mason; Robert A. Warner; Christopher F. G. Jeffrey; Anne M. Hoffman; Dennis A. Apeti; Simon J. Pittman (Environmental Monitoring and Assessment, 2014)

Long‐term changes in liana abundance and forest dynamics in undisturbed Amazonian forests - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Jefferson J. Valsko; Mason Campbell; Philip M. Fearnside; Will Edwards; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Lianas (climbing woody vines) are important structural parasites of tropical trees and may be increasing in abundance in response to global‐change drivers. We assessed long‐term (∼14‐year) changes in liana abundance and forest dynamics within 36 1‐ha permanent plots spanning ∼600 km 2 of undisturbed rainforest in central Amazonia. Within each plot, we counted each liana stem (≥2 cm diameter) and measured its diameter at 1.3 m height, and then used these data to estimate liana aboveground biomass. An initial liana survey was completed in 1997–1999 and then repeated in 2012, using identical methods. Liana abundance in the plots increased by an average of 1.00% ± 0.88% per year, leading to a highly significant ( t = 6.58, df = 35, P t = 1.46, df = 35, P = 0.15; paired t tests). Liana size distributions shifted significantly (χ 2 = 191, df = 8, P We used long‐term data on rainfall and forest dynamics from our study site to test hypotheses about potential drivers of change in liana communities. Lianas generally increase with rainfall seasonality, but we found no significant trends over time (1997–2012) in five rainfall parameters (total annual rainfall, dry‐season rainfall, wet‐season rainfall, number of very dry months, CV of monthly rainfall). However, rates of tree mortality and recruitment have increased significantly over time in our plots, and general linear mixed‐effect models suggested that lianas were more abundant at sites with higher tree mortality and flatter topography. Rising concentrations of atmospheric CO 2 , which may stimulate liana growth, might also have promoted liana increases. Our findings clearly support the view that lianas are increasing in abundance in old‐growth tropical forests, possibly in response to accelerating forest dynamics and rising CO 2 concentrations. The aboveground biomass of trees was lowest in plots with abundant lianas, suggesting that lianas could reduce forest carbon storage and potentially alter forest dynamics if they continue to proliferate.

Bottom side‐roll feeding by humpback whales ( Megaptera novaeangliae ) in the southern Gulf of Maine, U.S.A - Colin Ware; David N. Wiley; Ari S. Friedlaender; Mason Weinrich; Elliott L. Hazen; Alessandro Bocconcelli; Susan E. Parks; Alison K. Stimpert; Mike A. Thompson; Kyler Abernathy (Marine Mammal Science, 2014)
Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags ( DTAG s) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls ( BSR s) to feed along the seafloor. We recorded 3,505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º to 38º. The median interval between sequential BSR s, by animal, ranged from 24.0 s to 63.6 s and animals tended to maintain a consistent BSR heading during long BSR series encompassing multiple dives. BSR s were most frequent between 2200 and 0400. We identify three classes of behavior: simple side‐roll, side‐roll inversion, and repetitive scooping. Results indicate that BSR feeding is a common technique in the study area and there is both coordination and noncoordination between animals. We argue that this behavior is not lunge feeding as normally characterized, because animals are moving slowly through the event. The behavior also leads to vulnerability to entanglement in bottom‐set fishing gear, a major mortality factor for the species.

Bimanual coordination in children: manipulation of object distance - Andrea H. Mason; Jennifer L. Bruyn; Jo-Anne C. Lazarus (Experimental Brain Research, 2013)

The Effects of Substrate Elastic Modulus on Neural Precursor Cell Behavior - Michelle L. Previtera; Mason Hui; Devendra Verma; Abdelhamid J. Shahin; Rene Schloss; Noshir A. Langrana (Annals of Biomedical Engineering, 2013)

Permeability of Wellbore-Cement Fractures Following Degradation by Carbonated Brine - Stuart D. C. Walsh; Wyatt L. Du Frane; Harris E. Mason; Susan A. Carroll (Rock Mechanics and Rock Engineering, 2013)

Outcome Evaluation of the National Cancer Institute Career Development Awards Program - Julie L. Mason; Ming Lei; Jessica M. Faupel-Badger; Erika P. Ginsburg; Yvette R. Seger; Leo DiJoseph; Joshua D. Schnell; Jonathan S. Wiest (Journal of Cancer Education, 2013)

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

Matriptase-2 inhibits HECV motility and tubule formation in vitro and tumour angiogenesis in vivo - Siobhan L. Webb; Andrew J. Sanders; Malcolm D. Mason; Wen G. Jiang (Molecular and Cellular Biochemistry, 2012)

Neuropsychological Function and Cerebral Metabolites in HIV-infected Youth - R. Nagarajan; M. K. Sarma; M. A. Thomas; L. Chang; U. Natha; M. Wright; J. Hayes; K. Nielsen-Saines; D. E. Michalik; J. Deville; J. A. Church; K. Mason; et al. (Journal of Neuroimmune Pharmacology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Deep‐sea bacteria enriched by oil and dispersant from the Deepwater Horizon spill - Jacob Bælum; Sharon Borglin; Romy Chakraborty; Julian L. Fortney; Regina Lamendella; Olivia U. Mason; Manfred Auer; Marcin Zemla; Markus Bill; Mark E. Conrad; Stephanie A. Malfatti; Susannah G. Tringe; et al. (Environmental Microbiology, 2012)
Summary The Deepwater Horizon oil spill resulted in a massive influx of hydrocarbons into the Gulf of Mexico (the Gulf). To better understand the fate of the oil, we enriched and isolated indigenous hydrocarbon‐degrading bacteria from deep, uncontaminated waters from the Gulf with oil (Macondo MC252) and dispersant used during the spill (COREXIT 9500). During 20 days of incubation at 5°C, CO 2 evolution, hydrocarbon concentrations and the microbial community composition were determined. Approximately 60% to 25% of the dissolved oil with or without COREXIT, respectively, was degraded, in addition to some hydrocarbons in the COREXIT. FeCl 2 addition initially increased respiration rates, but not the total amount of hydrocarbons degraded. 16S rRNA gene sequencing revealed a succession in the microbial community over time, with an increase in abundance of Colwellia and Oceanospirillales during the incubations. Flocs formed during incubations with oil and/or COREXIT in the absence of FeCl 2 . Synchrotron radiation‐based Fourier transform infrared (SR‐FTIR) spectromicroscopy revealed that the flocs were comprised of oil, carbohydrates and biomass. Colwellia were the dominant bacteria in the flocs. Colwellia sp. strain RC25 was isolated from one of the enrichments and confirmed to rapidly degrade high amounts (approximately 75%) of the MC252 oil at 5°C. Together these data highlight several features that provide Colwellia with the capacity to degrade oil in cold, deep marine habitats, including aggregation together with oil droplets into flocs and hydrocarbon degradation ability.

Characterization of organic chemical contaminants in sediments from Jobos Bay, Puerto Rico - Anthony S. Pait; David R. Whitall; Angel Dieppa; Sarah E. Newton; Lia Brune; Chris Caldow; Andrew L. Mason; Dennis A. Apeti; John D. Christensen (Environmental Monitoring and Assessment, 2012)

ENU mutagenesis in mice identifies candidate genes for hypogonadism - Jeffrey Weiss; Lisa A. Hurley; Rebecca M. Harris; Courtney Finlayson; Minghan Tong; Lisa A. Fisher; Jennifer L. Moran; David R. Beier; Christopher Mason; J. Larry Jameson (Mammalian Genome, 2012)

Atopic dermatitis in West Highland white terriers is associated with a 1.3-Mb region on CFA 17 - Joana B. Roque; Caroline A. O’Leary; David L. Duffy; Myat Kyaw-Tanner; Puya Gharahkhani; Linda Vogelnest; Kenneth Mason; Michael Shipstone; Melanie Latter (Immunogenetics, 2012)

Evaluation of Reference Genes for Expression Studies in Ash (Fraxinus spp.) - Loren Rivera-Vega; Praveen Mamidala; Jennifer L. Koch; Mary E. Mason; Omprakash Mittapalli (Plant Molecular Biology Reporter, 2012)

Recapitulation of Werner syndrome sensitivity to camptothecin by limited knockdown of the WRN helicase/exonuclease - Joseph L. E. Bird; Katrin C. B. Jennert-Burston; Marcus A. Bachler; Penelope A. Mason; Jill E. Lowe; Seok-Jin Heo; Judith Campisi; Richard G. A. Faragher; Lynne S. Cox (Biogerontology, 2012)

The Neuroprotective Effect of Genetic Mannose-Binding Lectin Deficiency Is Not Sustained in the Subacute Phase of Stroke - Andrew F. Ducruet; Sergey A. Sosunov; Brad E. Zacharia; Justin Gorski; Mason L. Yeh; Peter DeRosa; Gregory Cohen; Paul R. Gigante; E. Sander Connolly (Translational Stroke Research, 2011)

Reduced MHC class II diversity in island compared to mainland populations of the black-footed rock-wallaby (Petrogale lateralis lateralis) - Robert A. B. Mason; Teena L. Browning; Mark D. B. Eldridge (Conservation Genetics, 2011)

Evidence that His349 acts as a pH-inducible switch to accelerate receptor-mediated iron release from the C-lobe of human transferrin - Ashley N. Steere; Shaina L. Byrne; N. Dennis Chasteen; Valerie C. Smith; Ross T. A. MacGillivray; Anne B. Mason (JBIC Journal of Biological Inorganic Chemistry, 2010)

Bimanual coordination in children: manipulation of object size - Andrea H. Mason; Jennifer L. Bruyn; Jo-Anne C. Lazarus (Experimental Brain Research, 2010)

Do new Access and Benefit Sharing procedures under the Convention on Biological Diversity threaten the future of biological control? - Matthew J. W. Cock; Joop C. van Lenteren; Jacques Brodeur; Barbara I. P. Barratt; Franz Bigler; Karel Bolckmans; Fernando L. Cônsoli; Fabian Haas; Peter G. Mason; José Roberto P. Parra (BioControl, 2010)

Diverse and often opposite behavioural effects of NMDA receptor antagonists in rats: implications for “NMDA antagonist modelling” of schizophrenia - Gary Gilmour; Elsa Y. Pioli; Sophie L. Dix; Janice W. Smith; Michael W. Conway; Wendy T. Jones; Sally Loomis; Rebecca Mason; Shahram Shahabi; Mark D. Tricklebank (Psychopharmacology, 2009)

Human serum transferrin: a tale of two lobes. Urea gel and steady state fluorescence analysis of recombinant transferrins as a function of pH, time, and the soluble portion of the transferrin receptor - Shaina L. Byrne; Anne B. Mason (JBIC Journal of Biological Inorganic Chemistry, 2009)

New hierarchical classification of food items for the assessment of exposure to packaging migrants: use of hub codes for different food groups - P. Northing; P.K.T. Oldring; L. Castle; P.A.S.S. Mason (Food Additives & Contaminants: Part A, 2009)

Hypoxia in a Coastal Embayment of the Chesapeake Bay: A Model Diagnostic Study of Oxygen Dynamics - Jian Shen; Taiping Wang; Julie Herman; Pam Mason; Gretchen L. Arnold (Estuaries and Coasts, 2008)

pH and expansin action on single suspension-cultured tomato (Lycopersicon esculentum) cells - C. X. Wang; L. Wang; S. J. McQueen-Mason; J. Pritchard; C. R. Thomas (Journal of Plant Research, 2008)

Macrofaunal recovery following TBT ban - R. Smith; S. G. Bolam; H. L. Rees; C. Mason (Environmental Monitoring and Assessment, 2007)

How consistent are trends in arrival (and departure) dates of migrant birds in the UK? - T. H. Sparks; K. Huber; R. L. Bland; H. Q. P. Crick; P. J. Croxton; J. Flood; R. G. Loxton; C. F. Mason; J. A. Newnham; P. Tryjanowski (Journal of Ornithology, 2007)

Preliminary evidence of reduced occipital GABA concentrations in puerperal women: a 1H-MRS study - C. Neill Epperson; Ralitza Gueorguieva; Kathryn A. Czarkowski; Stephanie Stiklus; Edward Sellers; John H. Krystal; Douglas L. Rothman; Graeme F. Mason (Psychopharmacology, 2006)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

A conserved functional role of pectic polymers in stomatal guard cells from a range of plant species - Louise Jones; Jennifer L. Milne; David Ashford; Maureen C. McCann; Simon J. McQueen-Mason (Planta, 2005)

Grip forces when passing an object to a partner - Andrea H. Mason; Christine L. MacKenzie (Experimental Brain Research, 2005)

A genetic linkage map of quinoa (Chenopodium quinoa) based on AFLP, RAPD, and SSR markers - P. J. Maughan; A. Bonifacio; E. N. Jellen; M. R. Stevens; C. E. Coleman; M. Ricks; S. L. Mason; D. E. Jarvis; B. W. Gardunia; D. J. Fairbanks (Theoretical and Applied Genetics, 2004)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

Stable Bacillus thuringiensis (Bt) toxin content in interspecific F 1 and backcross populations of wild Brassica rapa after Bt gene transfer - B. Zhu; J. R. Lawrence; S. I. Warwick; P. Mason; L. Braun; M.D. Halfhill; C. N. Stewart (Molecular Ecology, 2004)
Stable expression of a transgene may lead to increased fitness for wild plants after acquiring the transgene via crop–weed hybridization. Here, we investigate the stability of Bt toxin content in wild Brassica rapa acquiring the Bt gene from Bt Brassica napus . The Bt toxin content in nine Bt‐expressing B. napus lines was 0.80–1.70 µg/g leaf tissue throughout the growing season. These nine lines were crossed with three accessions of wild B. rapa and the Bt gene was successfully transferred to interspecific hybrids (F 1 ) and successive backcross generations (BC 1 to BC 4 ). The Bt toxin level in F 1 and BC progenies containing the Bt gene remained at 0.90–3.10 µg/g leaf tissue. This study indicates that the Bt gene can persist and be stably expressed in wild B. rapa .

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

Expression of the B subunit of Escherichia coli heat-labile enterotoxin as a fusion protein in transgenic tomato - A. M. Walmsley; M. L. Alvarez; Y. Jin; D. D. Kirk; S. M. Lee; J. Pinkhasov; M. M. Rigano; C. J. Arntzen; H. S. Mason (Plant Cell Reports, 2003)

Sex and strain-related differences in the peripheral blood cell values of inbred mouse strains - Benjamin T. Kile; Cammy L. Mason-Garrison; Monica J. Justice (Mammalian Genome, 2003)

Predatory Response of Brown Tree Snakes, to Chemical Stimuli from Human Skin - Michael J. Greene; Shantel L. Stark; Robert T. Mason (Journal of Chemical Ecology, 2002)

Sensitivity of seasonal climate forecasts to persisted SST anomalies - Goddard L.; Mason S. (Climate Dynamics, 2002)

Long‐range predictability of Zimbabwe summer rainfall - L. S. Unganai; S. J. Mason (International Journal of Climatology, 2002)
The potential for long‐range prediction of Zimbabwe summer rainfall is investigated using an analysis of variance approach. It is assumed that the variance between seasons (inter‐annual variability) is made up of two components: the climate noise (intra‐seasonal variability) and signal (any variance above the noise). The magnitude of the climate noise is estimated by computing the variance of time‐averaged rainfall data based on a statistical model whose parameters are derived from observed daily values at each station. Results from the study indicate that up to approximately 70% of the total variance in Zimbabwe summer rainfall is potentially predictable at long range. Predictability is greatest during the last half of the rainy season, January to March, and much lower during October to December. The south section of the country shows relatively more predictability than the north. Comparisons between signal and noise are discussed in the context of long‐range predictability. The natural variability (noise) is proposed as a lower limit of the standard error of the estimate for any long‐range precipitation forecast for the country. Copyright © 2002 Royal Meteorological Society.

Nuclear hormone receptors and cholesterol trafficking: the orphans find a new home - Michael L. Fitzgerald; Kathryn J. Moore; Mason W. Freeman (Journal of Molecular Medicine, 2002)

A 500 hPa synoptic wildland fire climatology for large Canadian forest fires, 1959-1996 - W. R. Skinner; M. D. Flannigan; B. J. Stocks; D. L. Martell; B. M. Wotton; J. B. Todd; J. A. Mason; K. A. Logan; E. M. Bosch (Theoretical and Applied Climatology, 2002)

Ecological processes influencing mortality of juvenile pink salmon ( Oncorhynchus gorbuscha ) in Prince William Sound, Alaska - T. M. Willette; R. T. Cooney; V. Patrick; D. M. Mason; G. L. Thomas; D. Scheel (Fisheries Oceanography, 2001)
Our collaborative work focused on understanding the system of mechanisms influencing the mortality of juvenile pink salmon ( Oncorhynchus gorbuscha ) in Prince William Sound, Alaska. Coordinated field studies, data analysis and numerical modelling projects were used to identify and explain the mechanisms and their roles in juvenile mortality. In particular, project studies addressed the identification of major fish and bird predators consuming juvenile salmon and the evaluation of three hypotheses linking these losses to (i) alternative prey for predators (prey‐switching hypothesis); (ii) salmon foraging behaviour (refuge‐dispersion hypothesis); and (iii) salmon size and growth (size‐refuge hypothesis). Two facultative planktivorous fishes, Pacific herring ( Clupea pallasi ) and walleye pollock ( Theragra chalcogramma ), probably consumed the most juvenile pink salmon each year, although other gadids were also important. Our prey‐switching hypothesis was supported by data indicating that herring and pollock switched to alternative nekton prey, including juvenile salmon, when the biomass of large copepods declined below about 0.2 g m −3 . Model simulations were consistent with these findings, but simulations suggested that a June pteropod bloom also sheltered juvenile salmon from predation. Our refuge‐dispersion hypothesis was supported by data indicating a five‐fold increase in predation losses of juvenile salmon when salmon dispersed from nearshore habitats as the biomass of large copepods declined. Our size‐refuge hypothesis was supported by data indicating that size‐ and growth‐dependent vulnerabilities of salmon to predators were a function of predator and prey sizes and the timing of predation events. Our model simulations offered support for the efficacy of representing ecological processes affecting juvenile fishes as systems of coupled evolution equations representing both spatial distribution and physiological status. Simulations wherein model dimensionality was limited through construction of composite trophic groups reproduced the dominant patterns in salmon survival data. In our study, these composite trophic groups were six key zooplankton taxonomic groups, two categories of adult pelagic fishes, and from six to 12 groups for tagged hatchery‐reared juvenile salmon. Model simulations also suggested the importance of salmon density and predator size as important factors modifying the predation process.

A synthesis of the life history and ecology of juvenile Pacific herring in Prince William Sound, Alaska - Brenda L. Norcross; Evelyn D. Brown; Robert J. Foy; Michele Frandsen; Shelton M. Gay; Thomas C. Kline; Doran M. Mason; E. Vincent Patrick; A. J. Paul; Kevin D. E. Stokesbury (Fisheries Oceanography, 2001)
Physical and biological variables affecting juvenile Pacific herring ( Clupea pallasi ) in Prince William Sound (PWS) from 1995 to 1998 were investigated as part of a multifaceted study of recruitment, the Sound Ecosystem Assessment (SEA) program. Though more herring larvae were retained in eastern PWS bays, ages‐0 and ‐1 herring used bays throughout PWS as nursery areas. Water transported into PWS from the Gulf of Alaska (GOA) contributed oceanic prey species to neritic habitats. Consequently, variations in local food availability resulted in different diets and growth rates of herring among bays. Summer food availability and possible interspecific competition for food in nursery areas affected the autumn nutritional status and juvenile whole body energy content (WBEC), which differed among bays. The WBEC of age‐0 herring in autumn was related to over‐winter survival. The limited amount of food consumption in winter was not sufficient to meet metabolic needs. The smallest age‐0 fish were most at risk of starvation in winter. Autumn WBEC of herring and winter water temperature were used to model over‐winter mortality of age‐0 herring. Differences in feeding and energetics among nursery areas indicated that habitat quality and age‐0 survival were varied among areas and years. These conditions were measured by temperature, zooplankton abundance, size of juvenile herring, diet energy, energy source (GOA vs. neritic zooplankton), WBEC, and within‐bay competition.

Pheromone Trailing Behavior of the Brown Tree Snake, Boiga irregularis - Michael J. Greene; Shantel L. Stark; Robert T. Mason (Journal of Chemical Ecology, 2001)

Current approaches to seasonal to interannual climate predictions - L. Goddard; S.J. Mason; S.E. Zebiak; C.F. Ropelewski; R. Basher; M.A. Cane (International Journal of Climatology, 2001)
This review paper presents an assessment of the current state of knowledge and capability in seasonal climate prediction at the end of the 20th century. The discussion covers the full range of issues involved in climate forecasting, including (1) the theory and empirical evidence for predictability; (2) predictions of surface boundary conditions, such as sea surface temperatures (SSTs) that drive the predictable part of the climate; (3) predictions of the climate; and (4) a brief consideration of the application of climate forecasts. Within this context, the research of the coming decades that seeks to address shortcomings in each area is described. Copyright © 2001 Royal Meteorological Society

Transmissibility of four tospoviruses by a thelytokous population ofThrips tabaci from Liguria, Northwestern Italy - R. Tedeschi; M. Ciuffo; G. Mason; P. Roggero; L. Tavella (Phytoparasitica, 2001)

TEMPORAL VARIABILITY IN FEATURES USED TO PHOTO‐IDENTIFY HUMPBACK WHALES ( MEGAPTERA NOVAEANGLIAE ) - Alexis L. Blackmer; Scott K. Anderson; Mason T. Weinrich (Marine Mammal Science, 2000)
A bstract Photographs of 99 humpback whales of known age were analyzed to assess the temporal variability and recognizability of individually distinctive fluke and dorsal fin features used for photo‐identification. Stable features tended to be morphological in nature (dorsal fin shape and edges, the trailing edge of the fluke, and the raised bumps on the caudal peduncle termed “knobs”). Transitory features typically were superficial marks (scarring, scratching, and pigmentation). The variability of several features was found to be age‐dependent as well. Young animals sometimes experienced substantial change to their fluke coloration patterns, though this feature stabilized with age. Dorsal fin edges and fluke serration peaks tended to undergo more change in males than in females, with most changes occurring following sexual maturation. Peduncle knobs were the most stable feature, with no documented change in any age interval. Given the extreme stability (and hence recognizability) of dorsal fin shape and peduncle knobs, we suggest that photographs combining the dorsal fin and the caudal peduncle provide the most consistent way to reidentify humpback whales, particularly calves following weaning.

Hydrogeomorphic (HGM) assessment—A test of user consistency - Dennis F. Whigham; Lyndon C. Lee; Mark M. Brinson; Richard D. Rheinhardt; Mark C. Rains; Jeffrey A. Mason; Humaira Kahn; Melanie B. Ruhlman; Wade L. Nutter (Wetlands, 1999)

Microstimulation of movements from cerebellar-receiving, but not pallidal-receiving areas of the macaque thalamus under ketamine anaesthesia - R. C. Miall; S. Price; R. Mason; R. E. Passingham; J. L. Winter; J. F. Stein (Experimental Brain Research, 1998)

Genetic analysis of shikimate dehydrogenase allozymes in Trifolium repens L. - W. M. Williams; K. M. Mason; M. L. Williamson (Theoretical and Applied Genetics, 1998)

A methodological appraisal of the impact of different classification procedures used in three different phases of the australian rheumatoid arthritis twin survey - N. Bellamy; D. L. Duffy; P. Sambrook; R. R. C. Buchanan; P. M. Brooks; H. Dunckley; S. C. Healey; S. Mason; N. G. Martin (Inflammopharmacology, 1998)

Climate Change and Forest Fire Potential in Russian and Canadian Boreal Forests - B. J. Stocks; M. A. Fosberg; T. J. Lynham; L. Mearns; B. M. Wotton; Q. Yang; J-Z. Jin; K. Lawrence; G. R. Hartley; J. A. Mason; D. W. McKENNEY (Climatic Change, 1998)

Aryl hydrocarbon hydroxylase and 16?-hydroxylase in cultured human lymphocytes - M. L. Coomes; W. A. Mason; I. E. Muijsson; E. T. Cantrell; D. E. Anderson; D. L. Busbee (Biochemical Genetics, 1976)